A high-safety electrode sheet and its preparation method and application
By adding a ring-shaped phosphorus-based monomer to the electrode slurry of the lithium-ion battery for in-situ polymerization, an electrode sheet containing phosphorus-based polymer material is generated, which solves the problem of thermal runaway in the lithium-ion battery and improves the safety of the battery and Cycle stability extends battery life.
Patent Information
- Application Number
- CN202111166335.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-30
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-09-30
AI Technical Summary
Due to the insufficient thermal stability and chemical stability of the organic liquid electrolyte used in lithium-ion batteries, thermal runaway occurs under conditions such as overcharge, short circuit, needle puncture, and high temperature. The existing flame retardant can only be effective at above 200℃ and Negative impact on battery performance.
Add a ring-shaped phosphorus-based monomer to the electrode slurry to generate a high-safe electrode sheet containing phosphorus-based polymer material through in-situ polymerization, reduce the surface activity of active material particles, inhibit side reactions with the electrolyte, and improve battery safety performance .
It significantly improves the safety and cycle stability of the battery, reduces the battery cell temperature, avoids fire and explosion, and only slightly reduces the energy density, extending the battery life.
Smart Images

Figure CN115911254B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a high-safety electrode sheet and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, long cycle life, low self-discharge rate and no memory effect, and have broad application prospects in the field of new energy electric vehicles. With the continuous development of science and technology, all walks of life have higher and higher requirements for the performance of lithium-ion batteries. With the continuous improvement of battery energy density, safety issues are becoming increasingly prominent.
[0003] Lithium-ion batteries face serious safety risks mainly because the electrolyte they use is an organic liquid electrolyte, which has insufficient thermal and chemical stability, making the battery prone to thermal runaway under conditions such as overcharging, short circuit, puncture, and high temperature. Currently, the electrolytes widely used in lithium-ion batteries are carbonate or ether electrolytes. In order to improve their safety, phosphorus-based compounds can be added to the electrolyte as flame retardants. Phosphorus-based flame retardants can produce phosphorus-based free radicals at high temperatures, cutting off the chain reaction during the combustion of the electrolyte, thereby achieving a flame retardant effect to a certain extent. For example, when the flame retardant trimethyl phosphate (TMP) is added to the electrolyte, its flame retardant mechanism is mainly that it first vaporizes when heated:
[0004] TMP(l)→TMP(g) (1)
[0005] Gaseous TMP molecules decompose under heat to release flame retardant free radicals (such as P free radicals):
[0006] TMP(g)→P(2)
[0007] The generated flame retardant free radicals have the ability to capture hydrogen free radicals in the system:
[0008] P+H→PH(3)
[0009] Thus, the chain reaction of hydrocarbon combustion or explosion is prevented. However, these phosphorus-based flame retardants can only exert their flame retardant effect at temperatures above 200°C. In addition, due to their high viscosity, high freezing point, chemical or electrochemical instability and other properties, they can only be used as additives and cannot fundamentally inhibit the temperature rise of the battery. In general, a large amount of phosphorus-based compounds needs to be added to achieve good results. The addition of excessive phosphorus-based compounds often has a negative impact on other aspects of the battery performance, such as reducing energy density, charge and discharge rate, cycle stability, etc., thereby greatly reducing the overall performance of the battery.
[0010] Therefore, it is urgent to develop a comprehensive solution that can suppress thermal runaway of battery cells, improve the safety of electrodes and battery cells, and ensure that the battery cells have good electrochemical performance. Summary of the invention
[0011] In order to solve the above problems, the present application provides a high-safety electrode sheet, which is prepared by mixing a phosphorus-based monomer containing a ring structure with an electrode slurry and coating it on a current collector, and then polymerizing it in situ to generate a high-safety electrode sheet containing a phosphorus-based polymer material. The in-situ mixing method in the electrode slurry is adopted to coat the surface of the electrode active material particles with a thin layer of polymer material containing phosphorus groups. Compared with general polymer electrolytes, the polymer layer has higher thermal stability and electrochemical stability, which can effectively reduce the surface activity of the electrode particles, reduce the direct contact between the active material particles and the electrolyte, inhibit the side reaction between the active material and the electrolyte, and improve the battery safety performance; in addition, the polymer layer can maintain a low interfacial impedance during the battery cycle, and at the same time homogenize the ion flow, so that the electrode has good capacity performance and cycle stability, and ensures the electrochemical performance of the battery.
[0012] According to one aspect of the present application, a high-safety electrode sheet is provided, comprising a current collector and an electrode material covered on the current collector, wherein the electrode material comprises an electrode active material, a conductive agent and a binder, and the high-safety electrode sheet is a positive electrode sheet and / or a negative electrode sheet; and further comprising a phosphorus-based polymer material formed by polymerization of monomers; the mass proportion of the phosphorus-based polymer material in the electrode material is 0.05 to 10%.
[0013] Optionally, the mass proportion of the phosphorus-based polymer material in the electrode material is 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any two of the values.
[0014] Preferably, the phosphorus-based polymer material accounts for 0.1% to 5% by mass of the electrode material.
[0015] If the content of phosphorus-based polymer material is less than 0.05%, it is difficult to coat a thin layer of phosphorus-containing polymer material on the surface of the electrode active material particles, and the improvement in battery safety is not obvious; if the content of phosphorus-based polymer material is greater than 10%, although it can greatly improve the safety of the battery, it will reduce the energy density and cycle performance of the battery, so it is 0.05-10%, and more preferably 0.1-5%.
[0016] Optionally, the monomer and the initiator are added during the slurry mixing process of the electrode material, and polymerized in situ to form the phosphorus-based polymer material.
[0017] Optionally, the weight proportions of the components in the electrode material are: 80-99 parts of electrode active material, 0.5-10 parts of conductive agent, 0.5-10 parts of binder, and 0.1-10 parts of monomer.
[0018] Optionally, the electrode active material is 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, 97 parts, 98 parts, 99 parts or any two parts.
[0019] Optionally, the conductive agent is 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or any two parts.
[0020] Optionally, the binder is 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or any two parts.
[0021] Optionally, the monomer is 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts or any two parts.
[0022] Optionally, the mass ratio of the monomer to the electrode active material is 0.1% to 5%.
[0023] Optionally, the mass ratio of the monomer to the electrode active material is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 3%, 3.5%, 4%, 4.5%, 5% or any two of the values.
[0024] Optionally, the phosphorus-based polymer material is obtained by blending at least one monomer with an electrode slurry and polymerizing it in situ.
[0025] Optionally, the monomer includes monomer A; the monomer A is at least one of the compounds shown in formula I,
[0026]
[0027] Wherein, M1 is selected from any one of C, N, P, S, and Si; R1 to R4 are independently selected from any one of a chain or a ring with no, with or without a substituent, and R1 contains at least one N; represents a cyclic structure; A1 represents that any position of the cyclic structure can be substituted by a substituent.
[0028] Optionally, the presence of the N atom helps to improve the ion transport performance and the ionic conductivity of the polymer material, thereby improving the cycle performance of the battery, enabling the battery to obtain better electrochemical performance, and improving the safety performance of the battery.
[0029] Optionally, the chain containing or not containing a substituent is a C1 to C 15 chain.
[0030] Optionally, the chain containing or not containing a substituent is a C1 chain, a C2 chain, a C3 chain, a C4 chain, a C5 chain, a C6 chain, a C7 chain, a C8 chain, a C9 chain, a C 10 Chain, C11 chain, C 12 Chain, C 13 Chain, C 14 Chain or C 15 chain.
[0031] Optionally, the chain containing or not containing a substituent is a C1 to C 10 chain.
[0032] Optionally, the chain containing or not containing a substituent is a C2-C6 chain containing or not containing a substituent.
[0033] Optionally, the chain containing or not containing a substituent is a saturated carbon chain, an unsaturated carbon chain, a saturated hetero chain, or an unsaturated hetero chain.
[0034] Optionally, the atoms on the chain containing or not containing substituents include at least one of C, S, N, O, P, B, and Si.
[0035] Optionally, the ring containing or not containing a substituent is a C3 to C 18 Ring.
[0036] Optionally, the ring containing or not containing a substituent is a C3 ring, a C4 ring, a C5 ring, a C6 ring, a C7 ring, a C8 ring, a C9 ring, a C 10 Ring, C 11 Ring, C 12 Ring, C13 Ring, C 14 Ring, C 15 Ring, C 16 Ring, C 17 Ring or C 18 ring.
[0037] Optionally, the ring containing or not containing a substituent is a C4-C 10 Ring.
[0038] Optionally, the ring containing or not containing a substituent is a C5-C8 ring containing or not containing a substituent.
[0039] Optionally, the ring containing or not containing a substituent includes a monocyclic ring, a linked ring, a fused ring, a bridged ring or a spirocyclic ring.
[0040] Optionally, the atoms on the ring containing or not containing substituents include at least one of C, P, S, Si, N, and O.
[0041] Optionally, the substituent includes at least one of H, a halogen atom, =O, =S, an alkyl group, a heteroalkyl group, an alkenyl group, a heteroalkenyl group, an alkynyl group, a heteroalkynyl group, a hydroxyl group, a carbonyl group, an aldehyde group, a carbonate group, a haloformyl group, a carboxyl group, an ester group, a peroxy group, an amine group (primary amine, secondary amine, tertiary amine, quaternary ammonium salt), an imino group (C=N), an imide (C(=O)NC(=O)), an azo group, a nitrate ester (RONO2), a phosphate ester group, a thioether group, a disulfide group, a cyano group, a sulfonic acid group, a sulfonyl group, an amide group, a nitro group, a pyridyl group, an acyloxy group, a phenyl group, a benzyl group, a benzyloxy group, a phenoxy group, an acetyl group, a benzoyl group, and a benzyloxycarbonyl group.
[0042] Optionally, any H in the substituent may be substituted by halogen.
[0043] Preferably, any H in the substituents can be replaced by F.
[0044] Optionally, R4 is independently selected from none, C1 to C 10 Any of a saturated carbon chain or an unsaturated carbon chain.
[0045] Optionally, R3 is selected from or -OLi.
[0046] Preferably, R3 is R4 is none.
[0047] The substituent directly connected to P contains a ring structure, which can make the battery safer and have better electrochemical performance and extend the service life of the battery.
[0048] Optionally, the The cyclic structure represented by is selected from a monocyclic or polycyclic ring, the monocyclic ring is selected from a three- to twelve-membered saturated carbocyclic ring, a saturated heterocyclic ring, an unsaturated carbocyclic ring or an unsaturated heterocyclic ring, and the polycyclic ring is selected from a fused ring, a bridged ring, a spiro ring, and a linked ring formed by combining any two of the monocyclic rings based on the monocyclic ring.
[0049] Preferably, the monocyclic ring is selected from a five- to six-membered unsaturated carbocyclic ring or an unsaturated heterocyclic ring;
[0050] Preferably, the monocyclic ring is selected from a five- to six-membered unsaturated heterocyclic ring.
[0051] Optionally, R1 is selected from at least one of the compounds shown in Formula II,
[0052]
[0053] Wherein, R7 to R8 are independently selected from any one of a chain or a ring without, with or without a substituent, and R8 contains at least one R9 is selected from any one of H, a chain or a ring which may or may not have a substituent.
[0054] An N group is specifically connected between R7 and R8. The presence of the N group helps to improve the ion transport performance and the ionic conductivity of the polymer material, thereby improving the safety and cycle performance of the battery.
[0055] The structure containing an ester group between P and N can make the battery have better electrochemical performance, high initial efficiency, good capacity retention rate, and can improve the ability to suppress battery temperature rise, further improving the safety of the battery.
[0056] Optionally, The -O or =O in the group can be directly or indirectly connected to P or N.
[0057] Optionally, R8 also includes an unsaturated bond and / or a heteroatom; the unsaturated bond is selected from any one of a double bond and a triple bond; and the heteroatom is selected from at least one of N, O, P, S, Si, and F.
[0058] Optionally, R8 The -O or =O is directly connected to P.
[0059] The oxygen atom in the ester group is directly connected to phosphorus, which can make the charge flow within the molecule smoother and stabilize the entire molecular structure, thus having a better cooling effect.
[0060] Optionally, the P atom is connected to a C atom in the chain by at least one bond.
[0061] The P atom has at least one bond connected to the C atom on the chain, that is, there is a PC chain bond. Compared with all the bonds of all P atoms being directly connected to heteroatoms or rings, it can better promote the role of the phosphorus group and is more helpful to improve the safety of polymer materials.
[0062] Optionally, the monomer further comprises a monomer B; the monomer B is selected from at least one of the compounds shown in formula III,
[0063]
[0064] Wherein, M3 is selected from C, N, P, S, Si; R 12 ~R 14 Independently selected from any one of a chain or a ring with no substituent, with substituent or without substituent.
[0065] Optionally, R 14 It is selected from a ring or a chain containing at least one heteroatom, and any position of the ring or the chain can be substituted by a substituent.
[0066] Preferably, R 14 is selected from a ring or chain containing at least two heteroatoms and containing at least one =0 in the ring or chain.
[0067] Preferably, R 14 Selected from At least one of; wherein A1, A2 represent that the atoms on the ring / chain can be substituted by a substituent.
[0068] Optionally, the molar ratio of the monomer B to the monomer A is α, wherein 0<α≤1.
[0069] Optionally, the molar ratio α of the monomer B to the monomer A is 0.01, 0.02, 0.025, 0.05, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1 or any two of the values.
[0070] Optionally, the high-safety electrode sheets are positive electrode sheets and negative electrode sheets, that is, phosphorus-based polymer materials are added to the slurries for preparing positive and negative electrodes at the same time to obtain positive electrode sheets containing phosphorus-based polymer materials and negative electrode sheets containing phosphorus-based polymer materials.
[0071] Optionally, the battery includes a positive electrode plate containing a phosphorus-based polymer material and a negative electrode plate containing a phosphorus-based polymer material.
[0072] Both the positive and negative electrodes of the battery contain phosphorus-based polymer materials, which significantly improves the safety of the battery compared to batteries containing only one type of electrode.
[0073] According to another aspect of the present application, a method for preparing a high-safety electrode sheet as described above is provided, wherein the preparation method is in-situ polymerization.
[0074] Optionally, the preparation method comprises:
[0075] (1) taking the above-mentioned portions of electrode active material, conductive agent, binder, monomer, and initiator, and mixing them uniformly to prepare a mixed slurry;
[0076] (2) coating the mixed slurry on a current collector and polymerizing the mixed slurry in situ to obtain the high-safety electrode sheet;
[0077] In-situ polymerization conditions: in-situ polymerization temperature is 60-130°C, and in-situ polymerization time is 0.1-30min;
[0078] Optionally, the preparation method comprises: coating a mixture containing a monomer, an initiator and an electrode slurry on a current collector, and performing in-situ polymerization to obtain the high-safety electrode sheet.
[0079] Optionally, the in-situ polymerization temperature is 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or any two of the above values.
[0080] Optionally, the in situ polymerization time is 0.1 min, 0.2 min, 0.3 min, 0.4 min, 0.5 min, 0.6 min, 0.7 min, 0.8 min, 0.9 min, 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, 30 min or any two of the numerical values.
[0081] The mass of the initiator is 0.2% to 2% of the mass of the monomer. The coating conditions are as follows: the coating speed is 0.5 m / min to 80 m / min.
[0082] Optionally, the coating speed is 0.5 m / min, 0.6 m / min, 0.7 m / min, 0.8 m / min, 0.9 m / min, 1 m / min, 2 m / min, 3 m / min, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min, 10 m / min, 20 m / min, 30 m / min, 40 m / min, 50 m / min, 60 m / min, 70 m / min, 80 m / min or any two of the values.
[0083] Optionally, the mass of the initiator is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% of the mass of the monomer or any two of the values.
[0084] Optionally, the electrode slurry includes an electrode active material, a conductive agent and a binder.
[0085] Optionally, the mass ratio of the electrode active material, the conductive agent and the binder is (80-99): (0.5-10): (0.5-10).
[0086] Optionally, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, tert-butyl perbenzoate, and methyl ethyl ketone peroxide.
[0087] Optionally, the monomer includes monomer A and / or monomer B.
[0088] Optionally, the method for preparing the high-safety electrode sheet comprises:
[0089] (1) adding electrode active materials, conductive agents, binders, monomers and initiators to a solvent and mixing them evenly to obtain a mixed slurry with a certain fluidity; (2) coating the mixed slurry in step (1) onto a current collector, controlling the coating speed to be 0.5 m / min to 80 m / min, baking at 60 to 130° C. to initiate in-situ polymerization of the monomers for a time of 0.1 to 30 min, and then rolling to obtain a high-safety electrode sheet.
[0090] Optionally, the solvent is an organic solvent.
[0091] Optionally, the organic solvent is selected from at least one of ethylene carbonate, fluoroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl formate, ethyl formate, propyl formate, butyl formate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, δ-valerolactone, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 2-methyl-1,3-dioxolane, ethylene glycol dimethyl ether, polyethylene glycol, cyclopentane, triethylene glycol dimethyl ether, fluorinated 1,4-dimethoxybutane, bis(2,2,2-trifluoroethyl) ether, tetramethylsilane, and tetraethylene glycol dimethyl ether.
[0092] In the mixed slurry of the present application, there is no limitation on the manner and order of adding the electrode active material, conductive agent, binder, monomer and initiator, and they can be added together or in batches.
[0093] Preferably, the electrode active material and the conductive agent are first added to the solvent, and then the monomer, the initiator and the binder are added after being mixed evenly.
[0094] This is because during the mixing process, the material will have a temperature rise, which will trigger in-situ polymerization of some monomers. In order to reduce polymerization, the monomer and initiator can be added in the latter order. In addition, when CMC and SBR are used as negative electrode binders, SBR is prone to demulsification due to long-term high-speed stirring, which will destroy its structure and reduce adhesion. Therefore, SBR is added last and stirred at a low speed.
[0095] Optionally, the mixed slurry further includes an auxiliary agent; the auxiliary agent includes at least one of lithium salt, inorganic oxide particles and fast ion conductor.
[0096] Optionally, the lithium salt is selected from one or more of lithium trifluoromethanesulfonate (LiCF3SO2), lithium bis(trifluoromethanesulfonic acid)imide (LiN(CF3SO2)2), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium chloride (LiCl), lithium iodide (LiI), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium hexafluoroarsenate (LiAsF6).
[0097] Optionally, the inorganic oxide particles are selected from SiO2, ZrO2, Al2O3, TiO2, BaTiO3, CeO2, CuO, ZnO, MnO, MnO2, silicates, aluminosilicates, borosilicates and formula A x B y O zAt least one in the group consisting of oxygen-containing salts, or at least one of the functionalized inorganic particles; wherein A is an alkali metal or an alkaline earth metal; B is selected from at least one of Al, Mn, Si, Ti, Zn, Zr, Fe, and Cu; x, y, and z are the numbers of the corresponding atoms such that the total charge of the oxygen-containing salt is 0.
[0098] Optionally, the fast ion conductor is an oxide solid electrolyte; the oxide solid electrolyte particles include at least one of the following compounds: Li 1+x1 Al x1 Ge 2-x1 (PO4)3 or its isomorphous heteroatom-doped compound, Li 1+x2 Al x2 Ti 2-x2 (PO4)3 or its isomorphous heteroatom-doped compound, perovskite-structured Li 3x3 La 2 / 3-x3 TiO3 or its isomorphous heteroatom-doped compound, Li 3 / 8 Sr 7 / 16 Ta 3 / 4 Hf 1 / 4 O3 or its isomorphous heteroatom-doped compound, Li 2x4-y1 Sr 1-x4 Ta y1 Zr 1-y1 O3 or its isomorphous heteroatom-doped compound, inverse perovskite-structured Li 3-2x5 M x5 HalO, Li3OCl or its isomorphous heteroatom-doped compound, LISICON-structured 2Li 4-x6 Si 1-x6 Px6O4 or its isomorphous heteroatom-doped compound, Li 14 ZnGe4O 16 or its isomorphous heteroatom-doped compound, garnet-structured Li 7-x7 La3Zr 2-x7 O 12 or its isomorphous heteroatom-doped compound; wherein, 0 < x1 ≤ 0.75, 0 < x2 ≤ 0.5, 0.06 ≤ x3 ≤ 0.14, 0.25 ≤ y1 ≤ 1, x4 = 0.75y1, 0 ≤ x5 ≤ 0.01, 0.5 ≤ x6 ≤ 0.6; 0 ≤ x7 < 1; M includes Mg 2+ , Ca 2+ , Sr 2+ or Ba 2+ or any combination of at least two of them; Hal is Cl or I.
[0099] The high-safety electrode sheet includes a positive electrode sheet and / or a negative electrode sheet.
[0100] Optionally, the positive electrode active material used in the positive electrode plate may include one or more of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium-rich manganese oxide, such as LiNi 0.83 Co 0.12 Mn 0.05 O2、LiNi 0.88 Co 0.09 Mn 0.03 O2、LiNi 0.8 Co 0.15 Al 0.05 At least one of O2.
[0101] The active material of the negative electrode may be one or more of graphite, silicon, soft carbon, hard carbon, silicon-carbon composite material, silicon-oxygen-carbon, lithium titanate, mesophase carbon microbeads, molybdenum disulfide, silicon oxide, silicon, metallic lithium or metallic lithium alloy.
[0102] Lithium cobalt oxide LiCoO2 is abbreviated as LCO, LiNi 0.88 Co 0.09 Mn 0.03 O2 is abbreviated as Ni88, LiNi 0.8 Co 0.15 Al 0.05 O2 is abbreviated as NCA.
[0103] Optionally, the phosphorus-based polymer material comprises one of the compounds having the structure of Formula IV, Formula V or Formula VI,
[0104]
[0105] Wherein, m is selected from 0.01 to 1, indicating that there is one in every 1 / m -[M1-M2]-polymer units. Connected to M1 or M2; p is selected from an integer between 10-10000, representing the degree of polymerization of the -[M1-CH2]- polymerization unit; n is selected from an integer between 5-1000, representing the degree of polymerization of the -[M3-CH2]- polymerization unit.
[0106] Optionally, m is selected from 0.01 to 1, such as 0.02, 0.05, 0.1, 0.2, 0.3, 0.5, 0.8, and 1, which means that there is one in every 1 / m -[M1-M2]-polymer units. Connected to M1 or M2. Can be omitted when m is 1.
[0107] Preferably, m is selected from 0.1 to 1.
[0108] Optionally, p is selected from an integer between 10 and 10000, such as 10, 20, 50, 80, 100, 500, 1000, 2000, 3000, 5000, 6000, 8000, and 10000, which represents that there are p -[M1-M2]- polymerization units in the structure of Formula 1.
[0109] Preferably, p is selected from an integer between 30 and 8000.
[0110] Optionally, n is selected from an integer between 5 and 1000, such as 10, 20, 30, 50, 80, 100, 150, 200, 250, 300, 350, 400, 450, 500, 600, 800, 900, 1000, etc., indicating that there are n -[M3-M4]- polymerization units in the structure.
[0111] Preferably, n is 10-800.
[0112] Preferably, p>n.
[0113] It should be noted that in the technical solution provided in the present application, no matter what synthesis method or process is used, a phosphorus-based polymer material as shown in Formula 1V, Formula V or Formula VI can be formed by the reaction of monomer A itself or the reaction between monomer A and monomer B. If in certain special cases, other products are obtained by the reaction of monomer A itself or monomer A and monomer B, these products are also within the scope of protection of the present application.
[0114] Optionally, the polymerized unit of the phosphorus-based polymer material may further include:
[0115] At least one of .
[0116] Due to limited space, other polymer units can be deduced by analogy and are not listed here one by one. The phosphorus-based polymer material structure composed of any combination of the above polymer units is within the protection scope of this application.
[0117] In the above structure, R is H, Li or BF3Li, A indicates that any position on the ring can be substituted by a halogen atom, an alkyl group or the like, in particular, by F, and the values of m, p and n can be found in the invention summary. The terminal group in the above structure can be any group, and this application does not limit this.
[0118] According to another aspect of the present application, a battery is provided, comprising at least one of the high-safety electrode sheets as described above and the high-safety electrode sheets obtained according to any of the preparation methods as described above.
[0119] Optionally, the battery may be a liquid battery, a hybrid solid-liquid battery or an all-solid-state battery (hybrid solid-liquid batteries and all-solid-state batteries are collectively referred to as solid-state batteries).
[0120] The battery comprises a battery cell and a packaging shell, wherein the battery cell comprises a positive electrode, a negative electrode and a separator arranged between the positive electrode and the negative electrode. The positive electrode and / or the negative electrode is an electrode sheet provided by the present invention or a high-safety electrode sheet prepared according to the method of the present invention. The separator can be one of a polyolefin separator, a cellulose separator, a polyimide separator, a polyamide separator, an aramid separator, a PE T non-woven separator, a ceramic coated separator, a solid electrolyte coated separator, and a PVDF coated separator; the packaging shell can be one of a soft-package aluminum-plastic film, a steel shell, an aluminum shell, and a cylinder.
[0121] In practical applications, the electrolyte may be an existing commercial electrolyte for lithium secondary batteries, or may be independently prepared. The present invention has no particular limitation on its composition and ratio.
[0122] Technical effects:
[0123] (1) The present application provides a novel high-safety electrode sheet system, which is prepared by mixing a phosphorus-based monomer containing a ring structure with an electrode slurry and coating the mixture on a current collector, and then polymerizing the mixture in situ to generate a high-safety electrode sheet containing a phosphorus-based polymer material. The phosphorus-based polymer material has a protective effect on the active material on the surface of the electrode sheet, can reduce the surface activity of the active particles of the electrode sheet, and inhibit the temperature rise of the battery, thereby significantly reducing the surface temperature of the battery cell, avoiding the dangers of fire and explosion of the battery; and achieving the goal of greatly improving the safety of the battery while taking into account the high energy density. It also has a strong anti-extrusion ability, and can maintain the structure and performance of the battery itself, thereby improving the safety of the battery, improving the cycle stability of the battery, and extending the service life of the battery.
[0124] (2) The present application uses an in-situ blending method in the electrode slurry to coat the surface of the electrode particles with a thin layer of polymer material containing phosphorus groups and cyclic structures. Compared with general polymer electrolytes, this polymer layer has higher thermal stability and electrochemical stability, which can effectively reduce the surface activity of the electrode particles, reduce the direct contact between the active material particles and the electrolyte, inhibit the side reactions between the active material and the electrolyte, and improve the battery safety performance; in addition, the polymer layer can maintain a low interfacial impedance during the battery cycle, while homogenizing the ion flow, so that the electrode has good capacity and cycle stability, and ensures the electrochemical performance of the battery. In addition, the in-situ curing preparation process is simple, safe and environmentally friendly, greatly reducing the use and emission of organic solvents, compatible with existing liquid battery processes, and easy to quickly promote industrialization. Compared with the non-in-situ curing process, the in-situ curing process can better improve the battery safety and electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0125] Figure 1 It is a comparison chart of battery cycle curves of battery 1-1, battery 1-2, battery 1-4 and blank battery 1 of the present application; the horizontal axis is the number of cycles, in units of times; the vertical axis is the capacity retention rate, in units of %.
[0126] Figure 2 It is a graph showing the battery puncture test results of battery 1-1(a), battery 1-2(b), battery 12-1(c), battery 1-11(d), battery 1-15(e) and blank battery 1(f) of the present application. DETAILED DESCRIPTION
[0127] The specific implementation of the present application is described below in conjunction with the accompanying drawings.
[0128] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. In addition, the reagents, materials and operating procedures used herein are reagents, materials and conventional procedures widely used in the corresponding fields. At the same time, in order to better understand the present invention, the definitions and explanations of the relevant terms are provided below.
[0129] In this example, the H NMR spectrum 1 In H NMR, s represents a singlet, d represents a doublet, t represents a triplet, q represents a quartet, m represents a multiplet (multiplet greater than four, such as a quintet, sextet, etc.), dd represents a doublet, and dt represents a doublet; the number before the bracket represents the chemical shift, and the number before H in the bracket represents the number of H, such as 2.22 (s, 2H), which means that there are two Hs with a chemical shift of 2.22, and the peak is a singlet. Other situations can be deduced by analogy and will not be repeated.
[0130] In this example, MS (ESI) m / z …… (MH) + Represents mass spectrum.
[0131] In the embodiments of the present application, 0.5C / 0.5C means charging at a rate of 0.5C and discharging at a rate of 0.5C.
[0132] In the embodiments of the present application, the corresponding substances of the English abbreviations are as follows: ethyl methyl carbonate (EMC), diethyl carbonate (DEC), ethylene carbonate (EC); lithium nitrate (LiNO3), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), lithium tetrafluorooxalate phosphate (LiPC2O2F4), 1,4-dimethoxybutane fluoride (FDMB), 1,3-propane sultone (1,3-PS), lithium difluorophosphate (LiPO2F2), vinylene carbonate (VC); lithium difluorooxalatoborate (LiODFB), lithium tetrafluoroborate (LiBF4), lithium hexafluorophosphate (LiPF6), lithium bis(fluoromethylsulfonyl)imide (LiFSI); azobisisobutyronitrile (AIBN), dibenzoyl peroxide (BPO).
[0133] In the present application, monomers for preparing phosphorus-based polymer materials are mixed in positive and negative electrode slurries, and through an in-situ curing process, pole pieces containing polymer materials are formed to further prepare the battery.
[0134] Wherein, the battery assembly also includes electrodes, a separator and an electrolyte membrane.
[0135] It should be noted that the application methods shown in the following examples are only preferred application methods for the monomer / battery material. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention. In addition, unless otherwise specified, all reagents used in the following examples are commercially available or can be synthesized according to the methods described herein or known methods. For reaction conditions not listed, they are also easily obtained by those skilled in the art. The operation methods without specific conditions in the following examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0136] Example 1
[0137] A high-safety electrode sheet comprises a current collector and an electrode material covering the current collector, wherein the electrode material comprises an electrode active material, a conductive agent and a binder, and the high-safety electrode sheet is a positive electrode sheet and / or a negative electrode sheet; and further comprises a phosphorus-based polymer material formed by monomer polymerization; and the mass proportion of the phosphorus-based polymer material in the electrode material is 0.05 to 10%.
[0138] Optionally, the monomer and the initiator are added during the slurry mixing process of the electrode material, and polymerized in situ to form the phosphorus-based polymer material.
[0139] Optionally, the weight proportions of the components in the electrode material are: 80-99 parts of electrode active material, 0.5-10 parts of conductive agent, 0.5-10 parts of binder, and 0.1-10 parts of phosphorus-based polymer material.
[0140] Optionally, the monomer includes monomer A; the monomer A is at least one of the compounds shown in formula I,
[0141]
[0142] Wherein, M1 is selected from any one of C, N, P, S, and Si; R1 to R4 are independently selected from any one of a chain or a ring with no, with or without a substituent, and R1 contains at least one N; represents a cyclic structure; A1 represents that any position of the cyclic structure can be substituted by a substituent.
[0143] Optionally, the presence of the N atom helps to improve the ion transport performance and the ionic conductivity of the polymer material, thereby improving the cycle performance of the battery and enabling the battery to obtain better electrochemical performance.
[0144] Optionally, R4 is independently selected from none, C1 to C 10 Any of a saturated carbon chain or an unsaturated carbon chain.
[0145] Optionally, R3 is selected from or -OLi.
[0146] Preferably, R3 is R4 is none.
[0147] The substituent directly connected to P contains a ring structure, which can make the battery safer and have better electrochemical performance and extend the service life of the battery.
[0148] Optionally, R1 is selected from at least one of the compounds shown in Formula II,
[0149]
[0150] Wherein, R7 to R8 are independently selected from any one of a chain or a ring without, with or without a substituent, and R8 contains at least one R9 is selected from any one of H, a chain or a ring which may or may not have a substituent.
[0151] An N group is specifically connected between R7 and R8. The presence of the N group helps to improve the ion transport performance and the ionic conductivity of the polymer material, thereby improving the safety and cycle performance of the battery.
[0152] The structure containing an ester group between P and N can make the battery have better electrochemical performance, high initial efficiency, good capacity retention rate, and can improve the ability to suppress battery temperature rise, further improving the safety of the battery.
[0153] Optionally, R8 also includes an unsaturated bond and / or a heteroatom; the unsaturated bond is selected from any one of a double bond and a triple bond; and the heteroatom is selected from at least one of N, O, P, S, Si, and F.
[0154] Optionally, R8 The -O or =O is directly connected to P.
[0155] The oxygen atom in the ester group is directly connected to phosphorus, which can make the charge flow within the molecule smoother and stabilize the entire molecular structure, thus having a better cooling effect.
[0156] Optionally, the P atom is connected to a C atom in the chain by at least one bond.
[0157] The P atom has at least one bond connected to the C atom on the chain, that is, there is a PC chain bond. Compared with all the bonds of all P atoms being directly connected to heteroatoms or rings, it can better promote the role of the phosphorus group and is more helpful to improve the safety of polymer materials.
[0158] Optionally, the monomer further comprises a monomer B; the monomer B is selected from at least one of the compounds shown in formula III,
[0159]
[0160] Wherein, M3 is selected from C, N, P, S, Si; R 12 -R 14 Independently selected from any one of a chain or a ring with no substituent, with substituent or without substituent.
[0161] Optionally, R 14 It is selected from a ring or a chain containing at least one heteroatom, and any position of the ring or the chain can be substituted by a substituent.
[0162] Preferably, R 14 is selected from a ring or chain containing at least two heteroatoms and containing at least one =0 in the ring or chain.
[0163] Optionally, the molar ratio of the monomer B to the monomer A is α, wherein 0<α≤1.
[0164] Example 2
[0165] A method for preparing a high-safety electrode sheet, the high-safety electrode sheet is consistent with the high-safety electrode sheet described in Example 1, and will not be described in detail here. The preparation method is prepared by in-situ polymerization. Specifically, the preparation method comprises:
[0166] (1) taking the above-mentioned electrode slurry, monomer and initiator, and mixing them evenly to prepare a mixed slurry; the electrode slurry comprises an electrode active material, a conductive agent and a binder;
[0167] (2) coating the mixed slurry on the current collector, and polymerizing in situ at a temperature of 60 to 130° C. for a reaction time of 0.1 to 30 min to obtain the electrode sheet; coating conditions: coating speed of 0.5 m / min to 80 m / min.
[0168] Optionally, the in-situ polymerization temperature is 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C or any two of the above values.
[0169] The mass of the initiator is 0.2% to 2% of the mass of the monomer.
[0170] Optionally, the mass of the initiator is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% of the mass of the monomer or any two of the values.
[0171] Optionally, the electrode slurry includes an electrode active material, a conductive agent and a binder.
[0172] Optionally, the mass ratio of the electrode active material, the conductive agent and the binder is (80-99): (0.5-10): (0.5-10).
[0173] Optionally, the initiator is selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, dibenzoyl peroxide, tert-butyl perbenzoate, and methyl ethyl ketone peroxide.
[0174] Optionally, the method for preparing the high-safety electrode sheet comprises:
[0175] (1) adding electrode active materials, conductive agents, binders, monomers and initiators to a solvent and mixing them evenly to obtain a mixed slurry with a certain fluidity; (2) coating the mixed slurry in step (1) onto a current collector, controlling the coating speed to be 0.5 m / min to 80 m / min, baking at 60 to 130° C. to initiate in-situ polymerization of the monomers for a time of 0.1 to 30 min, and then rolling to obtain a high-safety electrode sheet.
[0176] Optionally, the solvent is an organic solvent.
[0177] In the mixed slurry of the present application, there is no limitation on the manner and order of adding the electrode active material, conductive agent, binder, monomer and initiator, and they can be added together or in batches.
[0178] Preferably, the electrode active material and the conductive agent are first added to the solvent, and then the monomer, the initiator and the binder are added after being mixed evenly.
[0179] This is because during the mixing process, the material will have a temperature rise, which will trigger in-situ polymerization of some monomers. In order to reduce polymerization, the monomer and initiator can be added in the latter order. In addition, when CMC and SBR are used as negative electrode binders, SBR is prone to demulsification due to long-term high-speed stirring, which will destroy its structure and reduce adhesion. Therefore, SBR is added last and stirred at a low speed.
[0180] Optionally, the mixed slurry further includes an auxiliary agent; the auxiliary agent includes at least one of lithium salt, inorganic oxide particles and fast ion conductor.
[0181] Optionally, the method for preparing the positive electrode sheet includes:
[0182] S1: Under the condition of dew point temperature ≤-30℃, add positive electrode active material, conductive agent, binder, polymerizable monomer and initiator into solvent and mix evenly in a mixer. During the mixing process, the material will have temperature rise, which will induce in-situ polymerization of some monomers to obtain a slurry with certain fluidity; S2: Coat the slurry in S1 onto the current collector, control the coating speed to 0.5m / min~80m / min, bake at 60~130℃ for 0.1~30min to induce in-situ polymerization of monomers, and then roll to obtain the positive electrode sheet.
[0183] Preferably, the dew point temperature is ≤-45°C.
[0184] More preferably, the dew point temperature is ≤-60°C.
[0185] Optionally, the positive electrode active material includes LiCoO2, LiNi 0.88 Co 0.09 Mn 0.03 O2、LiNi 0.8 Co 0.15 Al 0.05 At least one of O2.
[0186] LiCoO2 is abbreviated as LCO, LiNi 0.88 Co 0.09 Mn 0.03 O2 is abbreviated as Ni88, LiNi 0.8 Co 0.15 Al 0.05 O2 is abbreviated as NCA.
[0187] Optionally, the method for preparing the negative electrode sheet includes:
[0188] S3: adding negative electrode active material, conductive agent, binder, polymerizable monomer and initiator into solvent and mixing them evenly in a mixer to obtain a slurry with certain fluidity; S4: coating the slurry in S3 onto the current collector, controlling the coating speed to be 0.5m / min~80m / min, baking at 60~130℃ for 0.1~30min to initiate in-situ polymerization of the monomer, and then rolling to obtain the negative electrode sheet.
[0189] It should be noted that in the technical solution provided in the present application, no matter what synthesis method or process is used, a phosphorus-based polymer material as shown in Formula 1V, Formula V or Formula VI can be formed by the reaction of monomer A itself or the reaction between monomer A and monomer B. If in certain special cases, other products are obtained by the reaction of monomer A itself or monomer A and monomer B, these products are also within the scope of protection of the present application.
[0190] Due to limited space, other polymer units can be deduced by analogy and are not listed here one by one. The phosphorus-based polymer material structure composed of any combination of the above polymer units is within the protection scope of this application.
[0191] In the above structure, R is H, Li or BF3Li, A indicates that any position on the ring can be substituted by a halogen atom, an alkyl group or the like, in particular, by F, and the values of m, p and n can be found in the invention summary. The terminal group in the above structure can be any group, and this application does not limit this.
[0192] Example 3
[0193] A battery, comprising at least one of the high-safety electrode sheet as described above and the high-safety electrode sheet obtained by any of the preparation methods as described above. The battery may be a liquid battery, a hybrid solid-liquid battery or an all-solid-state battery (hybrid solid-liquid batteries and all-solid-state batteries are collectively referred to as solid-state batteries)
[0194] Example 4
[0195] In practical applications, the electrolyte may be an existing commercial electrolyte for lithium secondary batteries, or may be independently prepared. The present invention has no particular limitation on its composition and ratio.
[0196] 1. Preparation of positive electrode slurry
[0197] The positive electrode active material, conductive agent, binder, and fast ion conductor are mixed uniformly according to the data ratios listed in Table 1 C1-C6 to obtain positive electrode slurries with a certain fluidity, which are named C1, C2, ... C6 respectively. Among them, the conductive agent is carbon nanotubes and conductive carbon black (CNT+Super-P, the mass ratio of the two is 1:2), and the binder is polyvinylidene fluoride (PVDF). The ratio is the mass ratio of the positive electrode active material, binder, conductive agent, and fast ion conductor.
[0198] The positive electrode materials are LiCoO2 (abbreviated as LCO), LiNi 0.88 Co 0.09 Mn 0.03 O2 (abbreviated as Ni88), LiNi 0.8 Co 0.15 Al 0.05 O2 (abbreviated as NCA). The fast ion conductor is Li 0.5 La 0.5 TiO3 (abbreviated as LLTO), Li 1.4 Al 0.4 Ti 1.6 (PO4)3 (abbreviated as LATP), Li 6.4 LqCy 1.6 Ta 0.6 O 12 (abbreviated as LLZO).
[0199] Table 1 Components and ratios of positive electrode slurry
[0200]
[0201] 2. Preparation of negative electrode slurry
[0202] Add the negative electrode active material, conductive agent and binder to deionized water according to the data listed in Table 2 and mix and stir evenly to obtain negative electrode slurries with certain fluidity, which are named F1, F2 and F3 respectively; or directly use metal lithium as the negative electrode F4. The ratio is the mass ratio of the negative electrode active material, the binder and the conductive agent.
[0203] Table 2 Components and ratios of negative electrode slurry
[0204] serial number Negative electrode active material Conductive agent Binder Proportion F1 Silicon Oxygen Carbon CNT+Super-P CMC+SBR 96:2:2 F2 Natural graphite CNT+Super-P CMC+SBR 96:2:2 F3 Silicon Carbon CNT+Super-P CMC+SBR 96:2:2 F4 Lithium Metal —— —— ——
[0205] The silicon-carbon material comes from Liyang Tianmu Pioneer Battery Material Technology Co., Ltd., SL450A-SOC; the silicon-oxygen-carbon material comes from BYD New Energy Materials Co., Ltd., S450-2A; the binder is sodium carboxymethyl cellulose and styrene-butadiene rubber (CMC+SBR).
[0206] 3. Diaphragm
[0207] Table 3 Diaphragm
[0208] serial number Diaphragm Specifications / Compartment S1 PP (polypropylene) double-sided ceramic 2+12+2 (12-substrate 2-alumina ceramic) S2 PE (polyethylene) double-sided ceramic 2+9+2 (9-substrate 2-alumina ceramic)
[0209] 4. Electrolyte
[0210] In practical applications, the electrolyte may be an existing commercial electrolyte for lithium secondary batteries, or may be independently prepared. The present invention has no particular limitation on its composition and ratio.
[0211] Table 4 Preparation of electrolyte
[0212]
[0213] Preparation method of blank battery:
[0214] As shown in Table 5-1, the negative electrode active material, conductive agent and binder are mixed evenly to form a negative electrode slurry, which is then coated on the copper foil to control the electrode surface capacity to 5.8 mAh / cm 2 , control the coating speed, blow dry and roll press to obtain a blank negative electrode sheet.
[0215] As shown in Table 5-1, the positive electrode active material, binder, conductive agent, and fast ion conductor are mixed evenly to form a positive electrode slurry, which is then coated on aluminum foil to control the electrode surface capacity to 5.5 mAh / cm 2 , blow dry and roll press to obtain a blank positive electrode sheet.
[0216] As shown in Table 5-1, the negative electrode sheets, positive electrode sheets and separators containing the above-mentioned battery materials are stacked and baked to obtain dry cells, and then the electrolyte is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the cell to be fully soaked to obtain a blank battery.
[0217] Experimental Example 1-1
[0218] Monomer A1: Monomer B1:
[0219] Preparation method of monomer A1: 0.02 mol of diphenylphosphoric acid, 0.02 mol of isocyanoethyl methacrylate, and 25 ml of dichloromethane are added to a 50 ml three-necked flask, stirred for 3 hours, and a dichloromethane solution containing 0.03 g of stannous isooctanoate is added dropwise through a constant pressure funnel, reacted at 5°C for 8 hours, and then the solvent is removed by reduced pressure distillation at 25°C to obtain monomer A1.
[0220] H NMR spectrum of monomer A1 1 H NMR (300MHz, DMSO, δppm): 6.76 (s, 1H), 7.72 (s, 4H), 7.46 (s, 6H), 4.58 (t, 2H), 3.15 (t, 2H), 2.01 (s, 3H), 6.48 (s, 1H), 6.40 (s, 1H).
[0221] Preparation method of monomer B1: 0.025 mol (4-aminophenyl)phosphonic acid (CAS: 5337-17-7) was dissolved in 25 ml of deionized water, and 0.050 mol of lithium hydroxide was added after sufficient stirring. The mixture was stirred at room temperature for 3 hours, and then the water was removed by rotary evaporation at 60°C. After drying, (4-aminophenyl) lithium phosphonate was obtained. 0.015 mol of (4-aminophenyl) lithium phosphonate and 0.015 mol of 3-isocyanate propylene were added to 20 ml of dichloromethane, and the mixture was stirred for 3 hours. A dichloromethane solution containing 0.020 g of stannous isooctanoate was added dropwise through a constant pressure funnel, and the mixture was reacted at 5°C for 4 hours. The mixture was then rotary evaporated at 40°C to remove the solvent, and monomer B1 was obtained.
[0222] Nuclear magnetic resonance hydrogen spectrum of monomer B1: 1H NMR (300 MHz, DMSO, δ ppm): 8.26 (s, 1H), 6.76 (s, 1H), 7.34 (d, 2H), 7.65 (d, 2H), 4.24 (d, 2H), 5.84 (m, 1H), 5.19 (d, 1H), 5.06 (d, 1H).
[0223] Preparation method of negative electrode sheet 1-1 and battery 1-1:
[0224] As shown in Table 5, monomers A1, B1 and initiator AIBN were mixed into the prepared negative electrode slurry F1 and mixed evenly, and coated on copper foil to control the electrode surface capacity to 5.8 mAh / cm 2 , control the coating speed, polymerize in situ at a certain temperature for a period of time, blow dry, and roll press to obtain the negative electrode sheet 1-1.
[0225] The positive electrode slurry C1 was coated on the aluminum foil, and the surface capacity of the control electrode was 5.5 mAh / cm 2 , blow drying, and roller pressing to obtain a positive electrode sheet 1-1.
[0226] The negative electrode sheet 1-1, the positive electrode sheet 1-1 and the separator S1 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E1 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery 1-1.
[0227] Experimental Example 1-2
[0228] Preparation method of negative electrode sheet 1-2 and battery 1-2:
[0229] The preparation method of the negative electrode sheet 1-2 is substantially the same as the preparation method of the negative electrode sheet 1-1, except that the monomers A1 and B1 are replaced by the monomer A1, and the remaining steps are the same to obtain the negative electrode sheet 1-2;
[0230] The preparation method of battery 1-2 is substantially the same as that of battery 1-1, except that negative electrode plate 1-1 is replaced by negative electrode plate 1-2, and the remaining steps are the same to obtain battery 1-2.
[0231] Comparative Examples 1-3
[0232] Preparation method of negative electrode sheet 1-3 and battery 1-3:
[0233] The preparation method of the negative electrode sheet 1-3 is substantially the same as the preparation method of the negative electrode sheet 1-1, except that the monomers A1 and B1 are replaced by the monomer B1, and the remaining steps are the same to obtain the negative electrode sheet 1-3;
[0234] The preparation method of battery 1-3 is substantially the same as that of battery 1-1, except that negative electrode plate 1-1 is replaced by negative electrode plate 1-3, and the remaining steps are the same to obtain battery 1-3.
[0235] Comparative Examples 1-4
[0236] Monomer D1:
[0237] The difference between the monomer D1 and the monomer A1 is that D1 does not contain a phosphorus group.
[0238] Preparation method of negative electrode sheet 1-4 and battery 1-4:
[0239] The preparation method of the negative electrode sheet 1-4 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is replaced by the monomer D1, and the remaining steps are the same to obtain the negative electrode sheet 1-4;
[0240] The preparation method of battery 1-4 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-4, and the remaining steps are the same to obtain battery 1-4.
[0241] Comparative Examples 1-5
[0242] Monomer D2:
[0243] The difference between the monomer D2 and the monomer A1 is that D2 does not contain a phosphorus group.
[0244] Preparation method of negative electrode sheet 1-5 and battery 1-5:
[0245] The preparation method of the negative electrode sheet 1-5 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is replaced by the monomer D2, and the remaining steps are the same to obtain the negative electrode sheet 1-5;
[0246] The preparation method of battery 1-5 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-5, and the remaining steps are the same to obtain battery 1-5.
[0247] Comparative Examples 1-6
[0248] Preparation method of negative electrode sheet 1-6 and battery 1-6:
[0249] The preparation method of the negative electrode sheet 1-6 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the initiator AIBN in Experimental Example 1-2 is not added, and the remaining steps are the same to obtain the negative electrode sheet 1-6;
[0250] The preparation method of battery 1-6 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-6, and the remaining steps are the same to obtain battery 1-6.
[0251] Due to the lack of initiator, monomer A1 does not polymerize.
[0252] Comparative Examples 1-7
[0253] Preparation method of negative electrode sheet 1-7 and battery 1-7:
[0254] The preparation method of the negative electrode sheet 1-7 is substantially the same as the preparation method of the negative electrode sheet 1-1, except that the initiator AIBN in Experimental Example 1-1 is not added, and the remaining steps are the same to obtain the negative electrode sheet 1-7;
[0255] The preparation method of battery 1-7 is substantially the same as that of battery 1-1, except that negative electrode plate 1-1 is replaced with negative electrode plate 1-7. The remaining steps are the same to obtain battery 1-7.
[0256] Due to the lack of initiator, monomer A1 and monomer B1 do not polymerize.
[0257] Comparative Examples 1-8
[0258] Monomer K1:
[0259] The difference between the monomer K1 and the monomer A1 is that K1 does not contain the N element.
[0260] Preparation method of negative electrode sheet 1-8 and battery 1-8:
[0261] The preparation method of the negative electrode sheet 1-8 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is replaced by the monomer K1, and the remaining steps are the same to obtain the negative electrode sheet 1-8;
[0262] The preparation method of battery 1-8 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-8, and the remaining steps are the same to obtain battery 1-8.
[0263] Comparative Examples 1-9
[0264] Monomer K2:
[0265] The difference between the monomer K2 and the monomer A1 is that K2 does not contain a cyclic structure.
[0266] Preparation method of negative electrode sheet 1-9 and battery 1-9:
[0267] The preparation method of the negative electrode sheet 1-9 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 is replaced by the monomer K2, and the remaining steps are the same to obtain the negative electrode sheet 1-9;
[0268] The preparation method of battery 1-9 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-9, and the remaining steps are the same to obtain battery 1-9.
[0269] Comparative Examples 1-10
[0270] Monomer K3:
[0271] Preparation method of negative electrode sheet 1-10 and battery 1-10:
[0272] The preparation method of the negative electrode sheet 1-10 is substantially the same as the preparation method of the negative electrode sheet 1-1, except that the monomers A1 and B1 are replaced with monomers A1 and K3, and the remaining steps are the same to obtain the negative electrode sheet 1-10;
[0273] The preparation method of battery 1-10 is substantially the same as that of battery 1-1, except that negative electrode plate 1-1 is replaced with negative electrode plate 1-10, and the remaining steps are the same to obtain battery 1-10.
[0274] Comparative Examples 1-11
[0275] Preparation method of negative electrode sheet 1-11 and battery 1-11:
[0276] The preparation method of the negative electrode sheet 1-11 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 and AIBN are not added, and the remaining steps are the same to obtain the negative electrode sheet 1-11;
[0277] The preparation method of battery 1-11 is roughly the same as that of battery 1-2, except that the negative electrode plate 1-2 is replaced by the negative electrode plate 1-11, and the monomer A1 and the initiator AIBN are added to the electrolyte E1. The positive electrode plate, the negative electrode plate and the separator are stacked and baked to obtain a dry battery cell, and the above-mentioned electrolyte is injected into the battery cell to initiate in-situ polymerization of the monomer at 60°C. The remaining steps are the same to obtain battery 1-11.
[0278] Comparative Examples 1-12
[0279] Preparation method of negative electrode sheet 1-12 and battery 1-12:
[0280] The preparation method of the negative electrode sheet 1-12 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomers A1 and AIBN are not added. The remaining steps are the same. After obtaining the negative electrode sheet, a solution containing A1 and AIBN is applied to the surface of the negative electrode sheet, and in-situ polymerization is performed at a certain temperature to obtain a negative electrode sheet 1-12 having a phosphorus-based polymer material on the surface.
[0281] The preparation method of battery 1-12 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-12, and the remaining steps are the same to obtain battery 1-12.
[0282] Comparative Examples 1-13
[0283] Preparation method of negative electrode sheet 1-13 and battery 1-13:
[0284] The preparation method of the negative electrode sheet 1-13 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 and AIBN are not added, and the remaining steps are the same to obtain the negative electrode sheet 1-13;
[0285] A solution containing A1 and AIBN is applied to the surface of the separator S1, and in-situ polymerization is initiated at 60° C. to obtain a separator 1-13 having a phosphorus-based polymer material on the surface;
[0286] The preparation method of battery 1-13 is substantially the same as that of battery 1-2. The negative electrode plate 1-2 is replaced by the negative electrode plate 1-13, and the diaphragm S1 is replaced by the diaphragm 1-13. The remaining steps are the same to obtain battery 1-13.
[0287] Comparative Examples 1-14
[0288] Preparation method of negative electrode sheet 1-14, positive electrode sheet 1-14 and battery 1-14:
[0289] Applying a solution containing A1 and AIBN to the surface of the positive electrode sheet 1-1, initiating in-situ polymerization of the monomers at 60° C., and obtaining a positive electrode sheet 1-14 having a phosphorus-based polymer material on the surface;
[0290] The preparation method of the negative electrode sheet 1-14 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that the monomer A1 and AIBN are not added, and the remaining steps are the same to obtain the negative electrode sheet 1-14;
[0291] The preparation method of battery 1-14 is substantially the same as that of battery 1-2, except that the negative electrode sheet 1-2 is replaced by the negative electrode sheet 1-14, and the positive electrode sheet 1-1 is replaced by the positive electrode sheet 1-14. The remaining steps are the same to obtain battery 1-14.
[0292] Comparative Examples 1-15
[0293] Preparation method of negative electrode sheet 1-15 and battery 1-15:
[0294] First, monomer A1 is in situ polymerized at 60°C under the action of initiator AIBN to obtain polymer material G1-15, and then polymer material G1-15 is mixed into negative electrode slurry F1 and mixed evenly. The remaining steps are roughly the same as the preparation method of negative electrode plate 1-2 to obtain negative electrode plate 1-15.
[0295] The preparation method of battery 1-15 is substantially the same as that of battery 1-2. The negative electrode plate 1-2 is replaced with the negative electrode plate 1-15. The remaining steps are the same to obtain battery 1-15.
[0296] Comparative Examples 1-16
[0297] First, monomers A1 and AIBN were added to E1 and stirred to form a uniform solution, and then in-situ polymerized at 60° C. to obtain polymer electrolyte E1-16.
[0298] The preparation method of battery 1-16 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate F1, and electrolyte E1 is replaced by electrolyte E1-16. The remaining steps are the same to obtain battery 1-16.
[0299] Comparative Examples 1-17
[0300] Monomer K4: Trimethyl phosphate (TMP)
[0301] The preparation method of battery 1-17 is roughly the same as that of blank battery 1, except that K4 accounting for 1% by mass of the negative electrode active material is added to the electrolyte E1. The remaining steps are the same to obtain battery 1-17.
[0302] Comparative Examples 1-18
[0303] Preparation method of negative electrode sheet 1-18 and battery 1-18:
[0304] The preparation method of the negative electrode sheet 1-18 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that 1% of the monomer A1 of the electrode active material is replaced with 0.04% of the monomer A1, and the amount of the initiator is adjusted accordingly according to the amount of the monomer A1. The remaining steps are the same, and the negative electrode sheet 1-18 can be obtained.
[0305] The preparation method of battery 1-18 is substantially the same as that of battery 1-2, except that negative electrode plate 1-2 is replaced by negative electrode plate 1-18, and the remaining steps are the same to obtain battery 1-2.
[0306] Comparative Examples 1-19
[0307] Preparation method of negative electrode sheet 1-19 and battery 1-19:
[0308] The preparation method of the negative electrode sheet 1-19 is substantially the same as the preparation method of the negative electrode sheet 1-2, except that 1% of the monomer A1 of the electrode active material is replaced with 11% of the monomer A1, and the amount of the initiator is adjusted accordingly according to the amount of the monomer A1. The remaining steps are the same, and the negative electrode sheet 1-19 can be obtained.
[0309] The preparation method of battery 1-19 is substantially the same as that of battery 1-2, except that the negative electrode plate 1-2 is replaced by the negative electrode plate 1-18, and the remaining steps are the same to obtain battery 1-2.
[0310] Experimental Example 2-1
[0311] Monomer A2: Monomer B2:
[0312] The preparation method of monomer A2 is shown in Experimental Example 1-1. (CAS: 838-85-7) and (CAS: 1476-23-9) was prepared by reaction.
[0313] Monomer A2: MS (ESI) m / z 333.08 (MH) + ; Monomer B2: MS (ESI) m / z 236.06 (MH) + .
[0314] Preparation method of monomer B2:
[0315]
[0316] Under nitrogen protection, 0.2 mmol 2mL dry dichloromethane was cooled to 0℃, and 0.2mmol of acryloyl chloride was added dropwise. After addition, the mixture was stirred for 1h, and then returned to room temperature for 1h. 5mL of water was added, and the mixture was extracted with 3×5mL of dichloromethane. The organic phases were combined, washed with saturated NaCl, dried over anhydrous sodium sulfate, filtered, and distilled under reduced pressure. The intermediate was obtained by column chromatography.
[0317] Under nitrogen protection, 0.2 mmol of the intermediate was added to a 25 mL Schlenk tube. 2 mL of dry tetrahydrofuran was cooled to -78°C, and n-butyl lithium n-hexane solution was added dropwise. After the addition, the mixture was stirred for 30 min, returned to room temperature and stirred for 1 h, and the product B2 was obtained by distillation under reduced pressure.
[0318] Preparation method of negative electrode sheet 2-1 and battery 2-1:
[0319] As shown in Table 5, monomers A2, B2 and initiator AIBN were mixed into the prepared negative electrode slurry F2 and mixed evenly, and coated on copper foil to control the electrode surface capacity to 5.8 mAh / cm 2 , controlling the coating speed, polymerizing in situ at a certain temperature for a period of time, air drying, and roller pressing to obtain a negative electrode sheet 2-1;
[0320] The positive electrode slurry C2 was coated on aluminum foil, and the surface capacity of the control electrode was 5.5 mAh / cm 2 , blow drying and roller pressing to obtain the positive electrode sheet 2-1.
[0321] The negative electrode sheet 2-1, the positive electrode sheet 2-1 and the separator S2 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E2 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery 2-1.
[0322] Experimental Example 2-2
[0323] Preparation method of negative electrode sheet 2-2 and battery 2-2:
[0324] The preparation method of the negative electrode sheet 2-2 is substantially the same as the preparation method of the negative electrode sheet 2-1, except that the monomers A2 and B2 are replaced by the monomer A2, and the remaining steps are the same to obtain the negative electrode sheet 2-2;
[0325] The preparation method of battery 2-2 is substantially the same as that of battery 2-1, except that negative electrode plate 2-1 is replaced by negative electrode plate 2-2, and the remaining steps are the same to obtain battery 2-2.
[0326] Comparative Examples 2-3
[0327] Preparation method of negative electrode sheet 2-3 and battery 2-3:
[0328] The preparation method of the negative electrode sheet 2-3 is substantially the same as the preparation method of the negative electrode sheet 2-1, except that the monomers A2 and B2 and the initiator AIBN are not added, and the remaining steps are the same to obtain the negative electrode sheet 2-3;
[0329] The preparation method of battery 2-3 is roughly the same as that of battery 2-1. The negative electrode plate 2-1 is replaced with the negative electrode plate 2-3, and the monomers A2, B2 and the initiator AIBN are added to the electrolyte E2. The positive electrode plate, the negative electrode plate and the separator are stacked and baked to obtain a dry battery cell. The above electrolyte is injected into the battery cell, and the monomers are initiated to polymerize in situ at a certain temperature. The remaining steps are the same to obtain battery 2-3.
[0330] Experimental Example 3-1
[0331] Monomer A3: Monomer B3:
[0332] The preparation method of monomer A3 can refer to Experimental Example 1-1. (CAS: 838-85-7) and (CAS: 13641-96-8).
[0333] Monomer A3: MS (ESI) m / z 419.11 (MH) + .
[0334] Preparation method of monomer B3: Under nitrogen protection, add 0.2 mmol 1mmol pyridine, 2mmol vinyl alcohol, add 0.4mmol triethylamine dropwise, add 0.4mmol acetic anhydride dropwise after complete dissolution, heat to 90℃, stir for 2h, cool to room temperature, add 100μL water, heat to 90℃, stir for 1h, cool to room temperature, add 0.5mL ethyl acetate, distill under reduced pressure, add acetone / water = 9 / 1 mixed solution to the concentrate, add 600μL cyclohexylamine, cool to 4℃, recrystallize for 12h, filter to obtain a white solid Add ethanol to the solid and add dropwise under reflux until it no longer dissolves. Filter while hot to remove the insoluble matter. Cool the mother liquor to 4°C, filter it with suction, wash it with ethanol, and dry it to obtain Under nitrogen protection, 0.2 mmol 2 mL of dry tetrahydrofuran was added, cooled to -45°C, 0.2 mmol of lithium diisopropylamide was added dropwise, stirred for 30 min, returned to room temperature, filtered, washed with n-hexane, and dried to obtain monomer B3. MS (ESI) m / z 132.00 (MH) + .
[0335] Preparation method of negative electrode sheet 3-1 and battery 3-1:
[0336] As shown in Table 5, monomers A3, B3 and initiator AIBN were mixed into the prepared negative electrode slurry F3 and mixed evenly, and coated on copper foil to control the electrode surface capacity to 5.8 mAh / cm 2 , control the coating speed, polymerize in situ at a certain temperature for a period of time, blow dry, and roll press to obtain the negative electrode sheet 3-1.
[0337] The positive electrode slurry C3 was coated on aluminum foil, and the surface capacity of the control electrode was 5.5 mAh / cm 2 , blow drying and roller pressing to obtain the positive electrode sheet 3-1.
[0338] The negative electrode sheet 3-1, the positive electrode sheet 3-1 and the separator S2 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E3 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery 3-1.
[0339] Experimental Example 3-2
[0340] Preparation method of negative electrode sheet 3-2 and battery 3-2:
[0341] The preparation method of the negative electrode sheet 3-2 is substantially the same as the preparation method of the negative electrode sheet 3-1, except that the monomers A3 and B3 are replaced by the monomer A3, and the remaining steps are the same to obtain the negative electrode sheet 3-2;
[0342] The preparation method of battery 3-2 is substantially the same as that of battery 3-1, except that negative electrode plate 3-1 is replaced by negative electrode plate 3-2, and the remaining steps are the same to obtain battery 3-2.
[0343] Experimental Example 4-1
[0344] Monomer A4: Monomer B4:
[0345] The preparation method of monomer A4 can be found in Experimental Example 1-1. (CAS: 1707-03-5) and (CAS: 13641-96-8) was prepared by reaction. Monomer A4: MS (ESI) m / z 359.09 (MH) + .
[0346] Preparation method of monomer B4: Under nitrogen protection, add 0.2 mmol of 0.2mmol NaI, 2mL acetone, stirred, refluxed for 8h, cooled, added methanol to quench the reaction, vacuum distilled, column chromatography to obtain Under nitrogen protection, 0.2 mmol 2 mL of dry tetrahydrofuran was cooled to -78°C, and 0.2 mmol of n-butyl lithium n-hexane solution was added dropwise. After the addition was completed, the mixture was stirred for half an hour, returned to room temperature, and distilled under reduced pressure to obtain monomer B4. Monomer B4: MS (ESI) m / z 128.02 (MH) + .
[0347] Preparation method of negative electrode sheet 4-1 and battery 4-1:
[0348] As shown in Table 5, monomers A4, B4 and initiator AIBN were mixed into the prepared negative electrode slurry F3 and mixed evenly, and coated on copper foil to control the electrode surface capacity to 5.8 mAh / cm 2 , control the coating speed, polymerize in situ at a certain temperature for a period of time, blow dry, and roll press to obtain the negative electrode sheet 4-1.
[0349] The positive electrode slurry C3 was coated on aluminum foil, and the surface capacity of the control electrode was 5.5 mAh / cm 2 , blow drying and roller pressing to obtain the positive electrode sheet 4-1.
[0350] The negative electrode sheet 4-1, the positive electrode sheet 4-1 and the separator S1 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E4 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery 4-1.
[0351] Experimental Example 4-2
[0352] Preparation method of negative electrode sheet 4-2 and battery 4-2:
[0353] The preparation method of the negative electrode sheet 4-2 is substantially the same as the preparation method of the negative electrode sheet 4-1, except that the monomers A4 and B4 are replaced by the monomer A4, and the remaining steps are the same to obtain the negative electrode sheet 4-2;
[0354] The preparation method of battery 4-2 is substantially the same as that of battery 4-1, except that negative electrode plate 4-1 is replaced by negative electrode plate 4-2, and the remaining steps are the same to obtain battery 4-2.
[0355] Experimental Example 5-1
[0356] Monomer A5: Monomer B5:
[0357] Preparation method: The preparation method of monomers A5 and B5 can be found in Experimental Example 1-1. (CAS: 1707-03-5) and (CAS: 30674-80-7) was prepared by reaction. Monomer A5: MS (ESI) m / z 441.08 (MH) + .
[0358] Monomer B5 passed (CAS: 75732-50-2) and (CAS: 30674-80-7) was prepared by reaction. Monomer B5: MS (ESI) m / z 459.14 (MH) + .
[0359] Preparation method of positive electrode sheet 5-1 and battery 5-1:
[0360] According to the data listed in Table 5, under the condition of dew point ≤ -30°C, monomers A5, B5 and initiator BPO were mixed into the prepared positive electrode slurry C3 and mixed evenly, and then coated on aluminum foil to control the electrode surface capacity to 5.5 mAh / cm 2 , control the coating speed, polymerize in situ at a certain temperature for a period of time, blow dry, and roll press to obtain the positive electrode sheet 5-1.
[0361] The negative electrode slurry F3 was coated on the copper foil, and the surface capacity of the control electrode was 5.8 mAh / cm 2 The negative electrode sheet 5-1 is obtained by air drying and roller pressing.
[0362] The positive electrode sheet 5-1, the negative electrode sheet 5-1 and the separator S1 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E5 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery 5-1.
[0363] Experimental Example 5-2
[0364] Preparation method of positive electrode sheet 5-2 and battery 5-2:
[0365] The preparation method of the positive electrode sheet 5-2 is substantially the same as the preparation method of the positive electrode sheet 5-1, except that the monomers A5 and B5 are replaced by the monomer A5, and the remaining steps are the same to obtain the positive electrode sheet 5-2;
[0366] The preparation method of battery 5-2 is substantially the same as that of battery 5-1, except that positive electrode plate 5-1 is replaced by positive electrode plate 5-2, and the remaining steps are the same to obtain battery 5-2.
[0367] Comparative Example 5-3
[0368] Preparation method of positive electrode sheet 5-3 and battery 5-3:
[0369] The preparation method of the positive electrode sheet 5-3 is substantially the same as the preparation method of the positive electrode sheet 5-1, except that the monomers A5, B5 and BPO are not added, and the remaining steps are the same to obtain the positive electrode sheet 5-3;
[0370] The preparation method of battery 5-3 is roughly the same as that of battery 5-1, except that the positive electrode plate 5-1 is replaced by the positive electrode plate 5-3, and monomers A5, B5 and initiator BPO are added to the electrolyte E5; the positive electrode plates, negative electrode plates and separators are stacked and baked to obtain a dry battery cell, the above-mentioned electrolyte is injected into the battery cell, and the monomers are initiated to polymerize in situ at a certain temperature. The remaining steps are the same to obtain battery 5-3.
[0371] Comparative Example 5-4
[0372] Preparation method of positive electrode sheet 5-4 and battery 5-4:
[0373] The preparation method of the positive electrode sheet 5-4 is substantially the same as the preparation method of the positive electrode sheet 5-2, except that the monomer A5 and BPO are not added, and the remaining steps are the same to obtain the positive electrode sheet 5-4;
[0374] The preparation method of battery 5-4 is roughly the same as that of battery 5-2. The positive electrode plate 5-2 is replaced by the positive electrode plate 5-4, and the monomer A5 and the initiator BPO are added to the electrolyte E5; the positive electrode plate, the negative electrode plate and the separator are stacked and baked to obtain a dry battery cell, the above-mentioned electrolyte is injected into the battery cell, and the monomer is initiated to polymerize in situ at a certain temperature. The remaining steps are the same to obtain battery 5-4.
[0375] Experimental Example 6-1
[0376] Monomer A6: Monomer B6:
[0377] The preparation methods of monomers A6 and B6 can be found in Experimental Example 1-1. (CAS: 56806-74-7) and (CAS: 30674-80-7) was prepared by reaction. Monomer A6: MS (ESI) m / z 497.12 (MH) + .
[0378] Monomer B6 passed (CAS: 15486-54-1) and (CAS: 30674-80-7) was prepared by reaction. Monomer B6: MS (ESI) m / z 345.09 (MH) + .
[0379] Preparation method of positive electrode sheet 6-1 and battery 6-1:
[0380] According to the data listed in Table 5, under the condition of dew point ≤ -30°C, monomers A6, B6 and initiator BPO were mixed into the prepared positive electrode slurry C3 and mixed evenly, and then coated on aluminum foil to control the electrode surface capacity to 5.5 mAh / cm 2 , control the coating speed, polymerize in situ at a certain temperature for a period of time, blow dry, and roll press to obtain the positive electrode sheet 6-1.
[0381] The negative electrode slurry F3 was coated on the copper foil, and the surface capacity of the control electrode was 5.8 mAh / cm 2 The negative electrode sheet 6-1 is obtained by air drying and roller pressing.
[0382] The positive electrode sheet 6-1, negative electrode sheet 6-1 and separator S2 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E6 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery 6-1.
[0383] Experimental Example 6-2
[0384] Preparation method of positive electrode sheet 6-2 and battery 6-2:
[0385] The preparation method of the positive electrode sheet 6-2 is substantially the same as the preparation method of the positive electrode sheet 6-1, except that the monomers A6 and B6 are replaced by the monomer A6, and the remaining steps are the same to obtain the positive electrode sheet 6-2;
[0386] The preparation method of battery 6-2 is substantially the same as that of battery 6-1, except that positive electrode sheet 6-1 is replaced by positive electrode sheet 6-2, and the remaining steps are the same to obtain battery 6-2.
[0387] Comparative Example 6-3
[0388] Preparation method of positive electrode sheet 6-3 and battery 6-3:
[0389] Monomers A6 and B6 are in situ polymerized at 60°C under the action of initiator BPO to obtain polymer material G6-3, and then polymer material G6-3 is blended into positive electrode slurry C3 and mixed evenly. The remaining steps are the same as the preparation method of positive electrode sheet 6-1 to obtain positive electrode sheet 6-3.
[0390] The preparation method of battery 6-3 is substantially the same as that of battery 6-1. The positive electrode sheet 6-1 is replaced with the positive electrode sheet 6-3. The remaining steps are the same to obtain battery 6-3.
[0391] Experimental Example 7
[0392] Monomer A7: Monomer B7:
[0393] The preparation method of monomer A7 can be found in Experimental Example 1-1. (CAS: 29138-97-4) and (CAS: 30674-80-7) was prepared by reaction.
[0394] Preparation method of monomer B7: 0.01 mol of 4-fluoro-5-hydroxy-4-methyl-1,3-dioxolane-2-one 0.011 mol of methacrylic acid and 25 ml of toluene were mixed and added to a 50 ml three-necked flask. After sufficient stirring, the temperature was raised to 100°C, and then 0.0216 g of methylimidazole toluene solution was added. The mixture was reacted at 105°C for 5 hours, and then the solvent was removed by reduced pressure distillation at 100°C to obtain monomer B7. Monomer A7: MS (ESI) m / z 465.12 (MH) + . Monomer B7: MS (ESI) m / z 204.04 (MH) + .
[0395] Preparation method of positive electrode sheet 7 and battery 7:
[0396] According to the data listed in Table 5, under the condition of dew point ≤ -30°C, monomers A7, B7 and initiator AIBN were mixed into the prepared positive electrode slurry C4 and mixed evenly, and coated on aluminum foil, and the surface capacity of the control electrode was 5.5 mAh / cm 2 , control the coating speed, polymerize in situ at a certain temperature, blow dry, and roll press to obtain the positive electrode sheet 7.
[0397] Metal lithium is directly used as the negative electrode plate 7.
[0398] The positive electrode sheet 7, the negative electrode sheet 7 and the separator S2 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E4 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 7.
[0399] Experimental Example 8
[0400] Monomer A8: Monomer B8:
[0401] Preparation method of monomer A8: Under nitrogen protection, add 0.2 mmol 0.2mmol 2mL dry toluene, 0.2mmol p-toluenesulfonic acid monohydrate, after addition, stir and reflux for 4 hours, return to room temperature, add 5mL water to quench the reaction, extract the organic phase with 3×5mL dichloromethane, combine the organic phases, dry over anhydrous sodium sulfate, and distill under reduced pressure to obtain
[0402] Under nitrogen protection, 0.2 mmol of 0.2mmol NaI, 2mL acetone, stirred, refluxed for 8h, cooled, added methanol to quench the reaction, vacuum distilled, column chromatography to obtain
[0403] Under nitrogen protection, 0.2 mmol 2 mL of dry tetrahydrofuran was cooled to -78°C, and 0.2 mmol of n-butyl lithium n-hexane solution was added dropwise. After the addition was completed, the mixture was stirred for half an hour, returned to room temperature, and distilled under reduced pressure to obtain monomer A8.
[0404] Preparation method of monomer B8: The preparation method of monomer B8 can be referred to Experimental Example 1-1. Monomer B8 can be prepared by reacting with methacrylic acid to form synthetic amide.
[0405] H NMR spectrum of monomer A8 1 H NMR (300 MHz, DMSO, δ ppm): 6.76 (s, 1H), 7.22 (m, 2H), 7.16 (m, 2H), 4.58 (t, 2H), 3.15 (t, 2H), 2.01 (s, 3H), 6.48 (s, 1H), 6.40 (s, 1H). H NMR spectrum of monomer B8 1 H NMR (300MHz, DMSO, δppm): 8.41 (s, 1H), 5.30 (m, 1H), 4.75 (dd, 1H), 4.50 (dd, 1H), 3.29 (dd, 1H), 3.04 (dd, 1H), 1.98 (s, 3H), 5.79 (s, 1H), 5.72 (s, 1H).
[0406] Preparation method of positive electrode sheet 8 and battery 8:
[0407] According to the data listed in Table 5, under the condition of dew point ≤ -30°C, monomers A8, B8 and initiator BPO were mixed into the prepared positive electrode slurry C5 and mixed evenly, and then coated on aluminum foil to control the surface capacity of the electrode to 5.5 mAh / cm 2 , control the coating speed, polymerize in situ at a certain temperature, blow dry, and roll press to obtain the positive electrode sheet 8.
[0408] The negative electrode slurry F1 was coated on the copper foil, and the surface capacity of the control electrode was 5.8 mAh / cm 2 The negative electrode sheet 8 is obtained by air drying and roller pressing.
[0409] The positive electrode sheet 8, negative electrode sheet 8 and separator S1 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E4 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 8.
[0410] Experimental Example 9
[0411] Monomer A9: Monomer B9:
[0412] Preparation method: The preparation method of monomer A9 can be found in Experimental Example 1-1. (CAS: 1130741-13-7) and (CAS: 32772-93-3) was prepared by reaction. B9 is an existing substance, CAS: 2050472-43-8.
[0413] H NMR spectrum of monomer A9 1 H NMR (300MHz, DMSO, δppm): 9.21 (s, 1H), 9.12 (s, 2H), 8.75 (d, 2H), 8.28 (d, 2H), 7.54 (t, 2H), 4.13 (d, 1H), 3.66 (d, 1H).
[0414] H NMR spectrum of monomer B9 1 H NMR (300MHz, DMSO, δppm): 5.07 (s, 1H), 5.09 (s, 1H), 5.34 (d, 1H).
[0415] Preparation method of positive electrode sheet 9, negative electrode sheet 9 and battery 9:
[0416] As shown in Table 5, under the condition of dew point ≤ -30°C, monomers A9, B9 and initiator BPO were mixed into the prepared positive electrode slurry C6 and mixed evenly, and coated on aluminum foil, and the control electrode sheet capacity was 5.5 mAh / cm 2 , controlling the coating speed, in-situ polymerization at a certain temperature, air drying, and roller pressing to obtain a positive electrode sheet 9;
[0417] As shown in Table 5, monomers A9, B9 and initiator BPO were mixed into the prepared negative electrode slurry F1 and mixed evenly, and coated on copper foil to control the electrode surface capacity to 5.8 mAh / cm 2 , controlling the coating speed to be 0.5 m / min to 80 m / min, in-situ polymerization at a certain temperature, air drying, and roller pressing to obtain a negative electrode sheet 9;
[0418] The positive electrode sheet 9, the negative electrode sheet 9 and the separator S1 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E5 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked, thereby obtaining a solid-state battery 9.
[0419] Experimental Example 10-1
[0420] Monomer A10: Monomer B10:
[0421] A10 and B10 are existing substances, CAS 135129-96-3 and 1531602-26-2 respectively; Monomer A10: MS (ESI) m / z 317.08 (MH) + ; Monomer B10: MS (ESI) m / z 200.07 (MH) + .
[0422] Preparation method of positive electrode sheet 10-1, negative electrode sheet 10-1 and battery 10-1:
[0423] As shown in Table 5, under the condition of dew point ≤ -30°C, monomers A10, B10 and initiator AIBN were mixed into the prepared positive electrode slurry C1 and mixed evenly, and coated on aluminum foil, and the control electrode sheet capacity was 5.5 mAh / cm 2 , control the coating speed, polymerize in situ at a certain temperature, blow dry, and roll press to obtain the positive electrode sheet 10-1.
[0424] As shown in Table 5, monomers A10, B10 and initiator AIBN were mixed into the prepared negative electrode slurry F1 and mixed evenly, and coated on copper foil to control the electrode surface capacity to 5.8 mAh / cm 2 , controlling the coating speed to be 0.5 m / min to 80 m / min, in-situ polymerization at a certain temperature, air drying, and roller pressing to obtain a negative electrode sheet 10-1;
[0425] The positive electrode sheet 10-1, the negative electrode sheet 10-1 and the separator S1 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E1 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery 10-1.
[0426] Experimental Example 10-2
[0427] Preparation method of positive electrode sheet 10-2, negative electrode sheet 10-2 and battery 10-2:
[0428] The preparation method of the positive electrode sheet 10-2 is substantially the same as the preparation method of the positive electrode sheet 10-1, except that the monomers A10 and B10 are replaced by the monomer A10, and the remaining steps are the same to obtain the positive electrode sheet 10-2;
[0429] The preparation method of the negative electrode sheet 10-2 is substantially the same as the preparation method of the negative electrode sheet 10-1, except that the monomers A10 and B10 are replaced by the monomer A10, and the remaining steps are the same to obtain the negative electrode sheet 10-2;
[0430] The preparation method of battery 10-2 is substantially the same as that of battery 10-1, except that the positive electrode sheet 10-1 is replaced by the positive electrode sheet 10-2, and the negative electrode sheet 10-1 is replaced by the negative electrode sheet 10-2. The remaining steps are the same to obtain battery 10-2.
[0431] Comparative Example 10-3
[0432] Preparation method of positive electrode sheet 10-3, negative electrode sheet 10-3 and battery 10-3:
[0433] The preparation method of the positive electrode sheet 10-3 is substantially the same as the preparation method of the positive electrode sheet 10-1, except that the monomers A10 and B10 are replaced by the monomer B10, and the remaining steps are the same to obtain the positive electrode sheet 10-3;
[0434] The preparation method of the negative electrode sheet 10-3 is substantially the same as the preparation method of the negative electrode sheet 10-1, except that the monomers A10 and B10 are replaced by the monomer B10, and the remaining steps are the same to obtain the negative electrode sheet 10-3;
[0435] The preparation method of battery 10-2 is substantially the same as that of battery 10-1, except that the positive electrode sheet 10-1 is replaced by the positive electrode sheet 10-3, and the negative electrode sheet 10-1 is replaced by the negative electrode sheet 10-3. The remaining steps are the same to obtain battery 10-3.
[0436] Experimental Example 11
[0437] Monomer A11: Monomer B11:
[0438] A11 is an existing substance, CAS: 1613189-47-1, monomer A11: MS (ESI) m / z 373.11 (MH) + .
[0439] Preparation method of monomer B11: Under nitrogen protection, add 0.2mmol each, 2mL toluene, 0.2mmol p-toluenesulfonic acid monohydrate, reflux reaction for 4h, cool to room temperature, add 5mL water, extract with 3×5mL dichloromethane, combine the organic phases, wash with saturated brine, dry over anhydrous sodium sulfate, and distill under reduced pressure to obtain Under nitrogen protection, 0.2 mmol of Add 2 mL of dry tetrahydrofuran, cool to -78°C, dropwise add 0.4 mmol of n-butyl lithium, stir for 30 min after addition, return to room temperature and stir for 30 min, and distill under reduced pressure to obtain monomer B11. MS (ESI) m / z 212.04 (MH) + .
[0440] Preparation method of positive electrode sheet 11, negative electrode sheet 11 and battery 11:
[0441] According to the data listed in Table 5, under the condition of dew point ≤ -30°C, monomers A11, B11 and initiator BPO were mixed into the prepared positive electrode slurry C5 and mixed evenly, and coated on aluminum foil, and the surface capacity of the control electrode was 5.5 mAh / cm 2 , controlling the coating speed, in-situ polymerization at a certain temperature, air drying, and roller pressing to obtain a positive electrode sheet 11;
[0442] As shown in Table 5, monomers A11, B11 and initiator BPO were mixed into the prepared negative electrode slurry F2 and mixed evenly, and coated on copper foil to control the electrode surface capacity to 5.8 mAh / cm 2 , controlling the coating speed, in-situ polymerization at a certain temperature, air drying, and roller pressing to obtain a negative electrode sheet 11;
[0443] The positive electrode sheet 11, the negative electrode sheet 11 and the separator S2 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E6 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery 11.
[0444] Experimental Example 12-1
[0445] Monomer A12: Monomeric B12:
[0446] Preparation method of monomer A12:
[0447] 0.01 mol 2-hydroxyethylphenylphosphoric acid (CAS: 2097974-02-0), 0.01mol (CAS: 14657-64-8) and 20 mL DMF were added to a round-bottom flask, reacted at 0.06 MPa and 110 °C for 10 h, then the solvent was removed at -0.1 MPa and 110 °C, CH2Cl2 was added, filtered, and rotary evaporated to obtain the intermediate product. Then add CH2Cl2 and 2-isocyanatomethacrylate (CAS: 30674-80-7) was reacted at room temperature for 30 h, and then the solvent was removed by rotary evaporation at 50°C to obtain A12.
[0448] Monomer B12 is an existing substance, CAS number is 1009107-26-9. Monomer A12: MS (ESI) m / z 447.36 (MH) +; Monomer B12: MS (ESI) m / z 142.00 (MH) + .
[0449] Preparation method of positive electrode sheet 12-1, negative electrode sheet 12-1 and battery 12-1:
[0450] As shown in Table 5, under the condition of dew point ≤ -30°C, monomers A12, B12 and initiator BPO were mixed into positive electrode slurry C1 and mixed evenly, and then coated on aluminum foil to control the surface capacity of the electrode to be 5.5 mAh / cm 2 , control the coating speed to 0.5 m / min to 80 m / min, perform in-situ polymerization at a certain temperature, blow dry, and roll press to obtain the positive electrode sheet 12 - 1.
[0451] As shown in Table 5, monomers A12, B12 and initiator BPO were mixed into the prepared negative electrode slurry F1 and mixed evenly, and coated on copper foil to control the electrode surface capacity to 5.8 mAh / cm 2 , controlling the coating speed, in-situ polymerization at a certain temperature, air drying, and roller pressing to obtain a negative electrode sheet 12-1;
[0452] The positive electrode sheet 12-1, the negative electrode sheet 12-1 and the separator S1 containing the battery materials are stacked and baked to obtain a dry battery cell, and then the electrolyte E1 is injected, the battery is packaged, and left to stand at room temperature for 12 hours to allow the battery cell to be fully soaked to obtain a solid-state battery 12-1.
[0453] Experimental Example 12-2
[0454] Preparation method of positive electrode sheet 12-2, negative electrode sheet 12-2 and battery 12-2:
[0455] The preparation method of the positive electrode sheet 12-2 is substantially the same as the preparation method of the positive electrode sheet 12-1, except that the monomers A12 and B12 are replaced by the monomer A12, and the remaining steps are the same to obtain the positive electrode sheet 12-2;
[0456] The preparation method of the negative electrode sheet 12-2 is substantially the same as the preparation method of the negative electrode sheet 12-1, except that the monomers A12 and B12 are replaced by the monomer A12, and the remaining steps are the same to obtain the negative electrode sheet 12-2;
[0457] The preparation method of battery 12-2 is substantially the same as that of battery 12-1, except that the positive electrode sheet 12-1 is replaced by the positive electrode sheet 12-2, and the negative electrode sheet 12-1 is replaced by the negative electrode sheet 12-2. The remaining steps are the same to obtain battery 12-2.
[0458] Comparative Example 12-3
[0459] Preparation method of positive electrode sheet 12-3, negative electrode sheet 12-3 and battery 12-3:
[0460] The preparation method of the positive electrode sheet 12-3 is substantially the same as the preparation method of the positive electrode sheet 12-1, except that the monomers A12 and B12 are replaced by the monomer B12, and the remaining steps are the same to obtain the positive electrode sheet 12-3;
[0461] The preparation method of the negative electrode sheet 12-3 is substantially the same as the preparation method of the negative electrode sheet 12-1, except that the monomers A12 and B12 are replaced by the monomer B12, and the remaining steps are the same to obtain the negative electrode sheet 12-3;
[0462] The preparation method of battery 12-3 is substantially the same as that of battery 12-1, except that the positive electrode sheet 12-1 is replaced by the positive electrode sheet 12-3, and the negative electrode sheet 12-1 is replaced by the negative electrode sheet 12-3. The remaining steps are the same to obtain battery 12-3.
[0463] Experimental Example 12-4
[0464] Preparation method of positive electrode sheet 12-4, negative electrode sheet 12-4 and battery 12-4:
[0465] The preparation method of the positive electrode sheet 12-4 is substantially the same as the preparation method of the positive electrode sheet 12-2, except that the monomer A12 and the initiator BPO are not added, and the remaining steps are the same to obtain the positive electrode sheet 12-4;
[0466] The preparation method of the negative electrode sheet 12-4 is exactly the same as the preparation method of the negative electrode sheet 12-2, and the negative electrode sheet 12-4 can be obtained;
[0467] The preparation method of battery 12-4 is substantially the same as that of battery 12-2, except that the positive electrode sheet 12-2 is replaced by the positive electrode sheet 12-4, and the negative electrode sheet 12-2 is replaced by the negative electrode sheet 12-4. The remaining steps are the same to obtain battery 12-4.
[0468] Experimental Example 12-5
[0469] Preparation method of positive electrode sheet 12-5, negative electrode sheet 12-5 and battery 12-5:
[0470] The preparation method of the positive electrode sheet 12-5 is exactly the same as the preparation method of the positive electrode sheet 12-2, and the positive electrode sheet 12-5 can be obtained;
[0471] The preparation method of the negative electrode sheet 12-5 is substantially the same as the preparation method of the negative electrode sheet 12-2, except that the monomer A12 and the initiator BPO are not added, and the remaining steps are the same to obtain the negative electrode sheet 12-5;
[0472] The preparation method of battery 12-5 is roughly the same as that of battery 12-2, except that the positive electrode sheet 12-2 is replaced by the positive electrode sheet 12-5, and the negative electrode sheet 12-2 is replaced by the negative electrode sheet 12-5. The remaining steps are the same to obtain battery 12-5.
[0473] Table 5-1 Experimental example battery configuration
[0474]
[0475]
[0476] Table 5-2 Preparation parameters of batteries in experimental examples and comparative examples
[0477]
[0478]
[0479] Battery Test
[0480] After the secondary battery was completely cured in situ, the first-week discharge capacity, first-week efficiency, and 400-cycle capacity retention rate of the battery were tested at room temperature. The test voltage range was 2.75 to 4.2 V, and the cycle mode was 0.5C / 0.5C (C represents the rate). The test results are shown in Table 6.
[0481] Table 6 Battery test results
[0482]
[0483]
[0484] The capacity retention rates of battery 7 and blank battery 5 in Table 6 are the capacity retention rates after 50 cycles of the battery, and the capacity retention rates of the remaining batteries are the capacity retention rates after 400 cycles.
[0485] The present application provides an electrode sheet, which is prepared by mixing a phosphorus-based monomer containing a ring structure with an electrode slurry and then coating the mixture on a current collector, and then subjecting the mixture to in-situ polymerization to generate an electrode sheet containing a phosphorus-based polymer material. The solid-state battery prepared using the electrode sheet greatly improves the cycle stability and safety of the battery and prolongs the battery life.
[0486] It can be seen from Table 6 that in the solid-state battery system with high nickel ternary (Ni88, NCA), lithium cobalt oxide as the positive electrode, and graphite, silicon carbon, silicon oxygen carbon, and metallic lithium as the negative electrode, compared with the blank battery, the energy density of the solid-state battery prepared by the present invention is only slightly reduced, but the cycle stability of the battery is significantly improved.
[0487] Electrode sheets are prepared by mixing monomers A and B in electrode slurry and initiating in-situ polymerization of the monomers. Solid-state batteries prepared from the electrode sheets (battery 1-1, battery 2-1, battery 3-1, battery 4-1, battery 5-1, battery 6-1, batteries 7 to 9, battery 10-1, battery 11, battery 12-1) have a battery capacity of 10.29Ah to 10.43Ah, a capacity retention rate of 93.23% to 93.87% after 400 cycles, and a capacity retention rate of 93.01% after 50 cycles of battery 7; battery 1-7 has a capacity of 9.62Ah and a capacity retention rate of 88.55% after 400 cycles. Although battery 1-7 also mixes monomers A+B in the electrode slurry, in-situ polymerization of the monomers is not initiated. Its electrical properties such as battery first-week efficiency, capacity, and cyclability are far less than those of the solid-state battery prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization. The solid-state battery 1-10 prepared by mixing monomers A and K3 in the electrode slurry and initiating in-situ polymerization to prepare the electrode sheet has a battery capacity of 9.91Ah and a capacity retention rate of 91.43% after 400 cycles, which is much smaller than the solid-state battery prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization, indicating that the monomers A+B in the present invention have higher cycle stability than A and acrylate. K3 in the battery 1-10 represents the acrylate of the prior art, and the effect of A1+K3 is much smaller than A1+B1 in the present application, indicating that only A1+B1 in the present application enables the battery to obtain better electrochemical performance, mainly because the monomer B of the present invention enables the solid-state battery to form a more stable SEI.
[0488] However, the electrode sheets are prepared by only mixing monomer A into the electrode slurry and initiating in-situ polymerization. The solid-state batteries prepared from the electrode sheets (battery 1-2, battery 2-2, battery 3-2, battery 4-2, battery 5-2, battery 6-2, battery 10-2, battery 12-2, battery 12-4, battery 12-5) have a battery capacity between 10.06 and 10.21 Ah, and a capacity retention rate of 92.27% to 92.54% after 400 cycles; the capacity of battery 1-6 is 9.56 Ah, and the capacity retention rate of 88.02% after 400 cycles. Although battery 1-6 also mixes monomer A into the electrode slurry, in-situ polymerization of the monomer is not initiated. Its electrical performance in terms of battery first-week efficiency, capacity, cyclability and other electrical properties is far less than that of the solid-state battery prepared by mixing monomer A into the electrode slurry and initiating in-situ polymerization.
[0489] The positive and negative electrode sheets are prepared by simultaneously mixing monomer A into the positive and negative electrode slurries and initiating in situ polymerization of the monomers. The solid-state battery 12-2 prepared from the positive and negative electrode sheets has a battery capacity of 10.13Ah and a capacity retention rate of 92.43% after 400 cycles. In terms of electrical properties such as the first-week efficiency, capacity, and cyclability, the performance is better than that of the solid-state batteries (battery 12-4 and battery 12-5) prepared by mixing monomer A into the electrode slurry of only the single electrode sheet and initiating in situ polymerization. This shows that the performance of the solid-state battery prepared by simultaneously mixing monomers in the positive and negative electrode slurries and initiating in situ polymerization is better than that of the battery mixed with single electrode slurries.
[0490] Electrode sheets are prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization of the monomers. The solid-state batteries prepared from the electrode sheets (battery 1-1, battery 2-1, battery 3-1, battery 4-1, battery 5-1, battery 6-1, batteries 7 to 9, battery 10-1, battery 11, battery 12-1) have a higher capacity retention rate after 400 cycles than the solid-state batteries (battery 1-2, battery 2-2, battery 3-2, battery 4-2, battery 5-2, battery 6-2, battery 10-2, battery 12-2, battery 12-4, battery 12-5) prepared by mixing only monomer A in the electrode slurry and initiating in-situ polymerization, indicating that the solid-state batteries prepared by simultaneously mixing monomers A and B in the electrode slurry and initiating in-situ polymerization of the monomers have higher cycle stability.
[0491] The solid-state batteries (batteries 1-3, 10-3, and 12-3) prepared using only the polymer generated by monomer B have a battery capacity between 9.86 and 9.89 Ah, and a capacity retention rate of 91.81% to 91.98% after 400 cycles; while the solid-state batteries (batteries 1-4 and 1-5) prepared using only monomer D have a battery capacity between 9.73 and 9.80 Ah, and a capacity retention rate of 89.34% to 89. 65%; solid-state batteries (batteries 1-8, batteries 1-9) prepared with monomers K1 and K2 have a battery capacity between 9.74 and 9.78 Ah, and a capacity retention rate of 91.33% to 91.45% after 400 cycles; while blank batteries 1 to 6 have a battery capacity between 10.01 and 10.11 Ah, a capacity retention rate of 91.13% to 91.41% after 400 cycles, and a capacity retention rate of 84.65% after 50 cycles of blank battery 5. This shows that the energy density of the solid-state battery prepared by the present invention is only slightly reduced, but the cycle stability of the battery is significantly improved.
[0492] Battery 1-17 adds the phosphorus-based flame retardant TMP to the electrolyte, and its performance in terms of first effect, capacity retention rate, etc. is lower than that of battery 1-1 and battery 1-2, further indicating that the present invention enables the electrode to have good capacity utilization and cycle stability. This is mainly because the present invention adopts an in-situ mixing method in the electrode slurry, so that the surface of the electrode active material particles is coated with a thin layer of phosphorus-containing polymer material. The polymer layer can maintain a low interfacial impedance during the battery cycle, while homogenizing the ion flow, thereby ensuring the electrochemical performance of the battery.
[0493] In the monomer A used in battery 10-2, there is an ester group between P and N; in the monomer A used in battery 12-2, there is no ester group between P and N. By comparing the electrochemical performance of the above batteries in terms of first efficiency, capacity retention rate, etc., it can be seen that in the structure of monomer A, the structure with an ester group between P and N can make the battery have better electrochemical performance.
[0494] The monomer K1 used in battery 1-8 does not contain N atoms, while the monomer A used in the batteries in other experimental examples contains N atoms. By comparing the electrochemical properties of the above batteries in terms of first effect, capacity retention rate, etc., it can be seen that the N atoms contained in monomer A are expected to enable the battery to obtain better electrochemical performance. Based on the inventor's previous research, the monomer K1 used in battery 1-8 can obtain higher first effect and cycle performance when used in a conventional battery system, but in order to obtain a battery with a mass specific energy close to 320Wh / kg, the present invention adopts a higher surface capacity electrode design and reduces the electrolyte content in the battery cell, but these operations have an adverse effect on other electrochemical properties of the battery, such as the first effect and cyclability; under such conditions, the solid-state battery prepared by the present invention still has relatively good electrochemical performance, proving that the N atoms contained in raw material A help improve the electrochemical performance of the battery.
[0495] In the monomer K2 used in batteries 1-9, the substituent connected to the P atom does not contain a ring structure, and in the monomer A used in the batteries in other experimental examples, the substituent connected to the P atom contains at least one ring structure. By comparing the electrochemical performance of the above batteries in terms of first efficiency and capacity retention rate, it can be seen that when the substituent connected to P in monomer A contains a ring structure, the battery has better electrochemical performance.
[0496] Battery 1-11 adds monomers to an electrolyte and injects the monomers into a battery cell to initiate in-situ polymerization of the monomers. Battery 1-12, battery 1-13 and battery 1-14 apply a precursor solution containing monomers to the surface of the positive / negative electrode or separator and then initiate in-situ polymerization of the monomers. Battery 1-15 first prepares a polymer material by in-situ polymerization of the monomers and then mixes the polymer material into the negative electrode slurry. Battery 1-16 prepares a solid electrolyte by in-situ polymerization of the monomers and then assembles a solid-state battery. In terms of first efficiency, capacity retention rate, etc., batteries 1-11 to 1-16 are slightly lower than battery 1-2, indicating that the electrode sheet and preparation method provided in the present application will not reduce the electrical performance of the battery, but will improve the first efficiency, capacity retention rate, etc. to a certain extent.
[0497] Battery 2-3, Battery 5-3 and Battery 5-4 all add monomers to the electrolyte and inject them into the battery cell to initiate in-situ polymerization of the monomers. The performance data of the electrical properties such as the first-week efficiency, capacity, and cyclability are much smaller than those of Battery 2-1, Battery 5-1 and Battery 5-2, indicating that the in-situ polymerization after mixing in the electrode slurry in this application has certain advantages.
[0498] Battery 6-3 first prepares the polymer material by in-situ polymerization of the monomer and then mixes the polymer material into the electrode slurry, which is different from the order of battery 6-1. However, the performance data of the electrical properties such as the first-week efficiency, capacity, and cyclability of battery 6-3 are lower than those of battery 6-1, indicating that the order of preparing the electrode sheets of the present application has certain advantages. Only by following the preparation method of the electrode sheets of the present application can good results be obtained.
[0499] It can be seen from battery 1-18, battery 1-2 and battery 1-19 that if the content of phosphorus-based polymer material is too high, the battery's electrical properties such as energy density and cycle performance will be significantly reduced.
[0500] Depend on Figure 1 It can be seen that the capacity retention rates of batteries 1-1 and 1-2 are much higher than those of comparative batteries 1-4 and blank battery 1, indicating that the present application can significantly improve the electrochemical performance of batteries by applying the electrode sheets prepared by in-situ blending of phosphorus-based monomers containing cyclic structures in the electrode slurry to the battery. The capacity retention rate of battery 1-1 is higher than that of battery 1-2, indicating that the solid-state battery prepared by blending monomers A+B in the electrode slurry and initiating in-situ polymerization has better cyclability than the solid-state battery prepared by blending only monomer A and initiating in-situ polymerization.
[0501] Battery safety performance test
[0502] The batteries prepared in the above experimental examples, the batteries prepared in the comparative examples and blank batteries 1-5 were subjected to acupuncture safety tests according to safety requirements and test methods for power batteries for electric vehicles in GB-T31485-2015 for lithium-ion batteries.
[0503] 1. Needle penetration test: The battery is charged at 1C constant current and constant voltage, with a cut-off current of 0.05C; a φ8mm high-temperature resistant steel needle is used to penetrate the battery plate at a speed of 25mm / s from a direction perpendicular to the battery plate. The penetration position should be close to the geometric center of the punctured surface, and the steel needle stays in the battery; observe for 1h, monitor the changes in the surface temperature of the battery cell during the process, and record whether the battery cell catches fire or explodes. The results are shown in Table 7.
[0504] Table 7 Cell acupuncture result record
[0505]
[0506]
[0507]
[0508] The present application provides an electrode sheet, which is prepared by mixing a phosphorus-based monomer containing a ring structure with an electrode slurry and then coating the mixture on a current collector, and then subjecting the mixture to in-situ polymerization to generate an electrode sheet containing a phosphorus-based polymer material. The solid-state battery prepared using the electrode sheet greatly improves the safety of the battery.
[0509] As shown in Table 7, the electrode sheets were prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization of the monomers. The solid-state batteries prepared from the electrode sheets (battery 1-1, battery 2-1, battery 3-1, battery 4-1, battery 5-1, battery 6-1, batteries 7-9, battery 10-1, battery 11, battery 12-1) did not catch fire or explode during the puncture test, and the surface temperature of the battery cell during puncture was 26.9-29.9°C, which significantly improved the battery safety. Although battery 1-7 also mixed monomers A and B in the electrode slurry, it did not initiate in-situ polymerization of the monomers. The battery caught fire and exploded during the puncture test, and the surface temperature of the battery cell during puncture was 536.2°C. The solid-state battery 1-10 prepared by mixing monomers A and K3 in the electrode slurry and initiating in-situ polymerization had a cell surface temperature of 43.6°C during needle puncture, which was much higher than the solid-state battery prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization, indicating that the monomer A+B in the present invention has higher safety performance than A and acrylate.
[0510] However, the solid-state batteries prepared by mixing monomer A in the electrode slurry and initiating in-situ polymerization (battery 1-2, battery 2-2, battery 3-2, battery 4-2, battery 5-2, battery 6-2, battery 10-2, battery 12-2, battery 12-4, battery 12-5) did not catch fire or explode during the puncture test, and the surface temperature of the battery cell was 32.1-39.9°C during the puncture test. Although battery 1-6 also mixed monomer A in the electrode slurry, it did not initiate in-situ polymerization of the monomer. The battery caught fire and exploded during the puncture test, and the surface temperature of the battery cell was 526.6°C during the puncture test.
[0511] The positive and negative electrodes were prepared by mixing monomer A into the electrode slurry and initiating in situ polymerization of the monomers. The solid-state battery (battery 12-2) prepared from the positive and negative electrodes had a cell surface temperature of 37.8°C during needle puncture, which was better than the solid-state batteries (batteries 12-4 and 12-5) prepared by only mixing monomer A into the electrode slurry of the monopole and initiating in situ polymerization. This shows that the solid-state battery prepared by simultaneously in situ mixing phosphorus-containing monomers in the positive and negative electrode slurries has higher safety and can simultaneously reduce the surface activity of the positive and negative electrode particles.
[0512] The electrode sheets are prepared by mixing monomers A and B in the electrode slurry and initiating in-situ polymerization of the monomers. The surface temperature of the cells of solid-state batteries (battery 1-1, battery 2-1, battery 3-1, battery 4-1, battery 5-1, battery 6-1, batteries 7 to 9, battery 10-1, battery 11, battery 12-1) prepared from the electrode sheets is lower during normal battery testing than that of solid-state batteries (battery 1-2, battery 2-2, battery 3-2, battery 4-2, battery 5-2, battery 6-2, battery 10-2, battery 12-2, battery 12-4, battery 12-5) prepared by mixing only monomer A in the electrode slurry and initiating in-situ polymerization, indicating that the solid-state batteries prepared by simultaneously mixing monomers A and B in the electrode slurry and initiating in-situ polymerization of the monomers have higher safety.
[0513] The solid-state batteries (battery 1-3, battery 10-3, battery 12-3) prepared using only the polymer generated by monomer B did not catch fire or explode when punctured, and the surface temperature of the battery cell was 483.8-498.7°C during puncture. The solid-state batteries (battery 1-4, battery 1-5) prepared using only monomer D caught fire or exploded when punctured, and the surface temperature of the battery cell was 595.5-598.0°C during puncture. The solid-state batteries (battery 1-8, battery 1-9) prepared using monomers K1 and K2 did not catch fire or explode when punctured, and the surface temperature of the battery cell was 78.7-79.2°C during puncture. Although the introduction of monomers K1 and K2 improves the safety of the battery to a certain extent, it is not enough to suppress the temperature rise of the battery; battery 1-17 added phosphorus-containing flame retardants to the electrolyte, and the battery caught fire and exploded when punctured, and the surface temperature of the battery cell was 456.8°C during puncture, indicating that adding the same amount of flame retardant as the monomer of the present invention to the electrolyte has no flame retardant effect at all, and the flame retardant cannot fundamentally suppress the temperature rise of the battery; while blank batteries 1 to 5 caught fire and exploded when punctured, and the surface temperature of the battery cell was 613.2 to 643.7°C during puncture, further indicating that the solid-state battery prepared by in-situ mixing of cyclic phosphorus-based monomers in the electrode slurry of the present invention can significantly improve the safety of the battery.
[0514] In the monomer A used in battery 10-2, there is an ester group between P and N, and the surface temperature of the battery cell after battery puncture is 32.1°C; in the monomer A of battery 12-2, there is no ester group between P and N, and the surface temperature of the battery cell after battery puncture is 37.8°C, which is higher than the surface temperature of battery 10-2, indicating that the ester group between P and N in monomer A is beneficial to further improve the safety of the battery; in the batteries prepared in all experimental examples, monomer A contains N atoms, and the surface temperature of the battery cell after battery puncture is between 27.0 and 39.9°C; monomer K1 of battery 1-8 does not contain N atoms, and the surface temperature of the battery cell after battery puncture is 78.7°C, which is higher than the temperature of the batteries prepared in all experimental examples. Although the introduction of K1 has a certain improvement on the battery safety, its ability to suppress the temperature rise of the battery is insufficient, further indicating that the presence of N in monomer A has better safety. In previous studies, monomer K1 can also significantly improve the safety performance of lithium-ion batteries. Its improvement in safety has been verified in 250-300Wh / kg cells, and the corresponding cells can successfully pass tests such as puncture, extrusion, collision, and 150°C thermal shock. However, in order to achieve higher specific energy, the battery provided by the present invention further increases the proportion of active substances in the cell, especially the surface capacity of the pole piece. Moreover, for high-nickel ternary materials, the higher the content of Ni element, the higher the corresponding battery energy density, and the more stringent the safety requirements, which makes the chain reaction of thermal runaway in the cell more likely to occur. In contrast, the present invention also achieves a higher specific energy (≥320Wh / kg), and its cell does not catch fire or explode during the puncture process, and has a lower cell surface temperature after puncture, which further shows that the monomer A containing N atoms in the structure helps to further improve the safety of the battery, especially in high-specific energy cells, the effect is more obvious. In the monomer A of the battery prepared in all experimental examples, the substituent directly connected to the P atom contains a cyclic structure, and the surface temperature of the battery cell after the battery is punctured is 27.0-39.9°C; in the monomer K2 of battery 1-9, the substituent directly connected to the P atom does not contain a cyclic structure, and the surface temperature of the battery after puncture is 79.2°C, indicating that although the introduction of K2 has a certain improvement on the battery safety, the ability to suppress the temperature rise of the battery is insufficient, further indicating that the cyclic structure in the substituent directly connected to the P atom in monomer A makes the battery safer. K3 in battery 1-10 represents the acrylate of the prior art, and the effect of A1+K3 is much smaller than A1+B1 in this application, indicating that the solid-state battery prepared in this application has higher safety. The monomer K1 used in battery 1-8 does not contain N atoms, and the monomer A used in the batteries in other experimental examples contains N atoms.
[0515] It can be seen from batteries 1-2, 1-18 and 1-19 that if the content of phosphorus-based polymer material is too little, it is difficult to coat a thin layer of polymer material containing phosphorus groups on the surface of the electrode active material particles, and the battery will catch fire or explode when punctured, and the battery safety will not be significantly improved; if the content of phosphorus-based polymer material is too much, the battery will not catch fire or explode when punctured, and although the battery safety can be greatly improved, the battery's electrical properties such as energy density and cycle performance will be reduced.
[0516] It can be seen from battery 1-2 and battery 1-11 to battery 1-16, battery 2-1 and battery 2-3, battery 5-1 and battery 5-3, battery 5-2 and 5-4, battery 6-1 and battery 6-3 that the solid-state batteries prepared by monomer A or A+B using the following methods all caught fire and exploded when punctured by acupuncture. These methods include: 1. directly adding monomers and initiators into electrolyte and then injecting them into the battery core to initiate in-situ polymerization of monomers to prepare solid-state batteries; 2. preparing monomers and initiators into precursor liquid and coating them on the positive electrode, negative electrode or diaphragm surface and then initiating in-situ polymerization of monomers; 3. first initiating monomer polymerization in vitro to prepare polymer materials, and then mixing them into electrode slurry; 4. initiating in-situ polymerization of monomers to prepare solid electrolytes and then assembling solid-state batteries. The present invention prepares an electrode sheet containing a phosphorus-based polymer material by mixing the monomer into the electrode slurry and initiating in-situ polymerization of the monomer. The solid-state battery prepared by the electrode sheet does not catch fire or explode when punctured by acupuncture. The above phenomenon further shows that the electrode sheet containing a phosphorus-based polymer material of the present application has higher safety. This is mainly because the present application adopts an in-situ blending method in the electrode slurry, so that the surface of the electrode active material particles is coated with a thin layer of polymer material containing phosphorus groups. Compared with general polymer electrolytes, this polymer layer has higher thermal stability and electrochemical stability, which can effectively reduce the surface activity of the electrode particles, reduce the direct contact between the active material particles and the electrolyte, inhibit the side reactions between the active material and the electrolyte, and improve the battery safety performance; in addition, the polymer layer can maintain a low interfacial impedance during the battery cycle, and at the same time homogenize the ion flow, so that the electrode has good capacity utilization and cycle stability, thereby ensuring the electrochemical performance of the battery.
[0517] from Figure 2 It can be seen more intuitively that the solid-state battery prepared by introducing monomer A or simultaneously introducing monomers A+B into the electrode slurry and initiating in-situ polymerization of the monomers in the present invention remains in good condition after acupuncture, while blank battery 1 and batteries 1-11 and 1-15 caught fire and exploded after acupuncture test and were severely damaged. This shows that the electrode sheet containing phosphorus-based polymer materials prepared by adding monomers to the electrode slurry and initiating in-situ polymerization provided in the present application can be applied to solid-state batteries, which can significantly improve the safety performance of the battery.
[0518] 2. Battery Thermal Shock Safety Test
[0519] The battery was charged at 1C constant current and constant voltage, with a cut-off current of 0.05C; heated at 180℃ for 2h: the heating rate was 5℃ / s, heated to 180℃ and kept warm for 2h, and observed for 1h; and recorded whether the battery caught fire or exploded. "No fire or explosion" means passed, otherwise failed. The test results are shown in Table 8.
[0520] Table 8 Battery thermal shock safety results record
[0521]
[0522]
[0523] The present application provides an electrode sheet, which is prepared by mixing a phosphorus-based monomer containing a ring structure with an electrode slurry and then coating the mixture on a current collector, and then subjecting the mixture to in-situ polymerization to generate an electrode sheet containing a phosphorus-based polymer material. The solid-state battery prepared using the electrode sheet greatly improves the safety of the battery.
[0524] As shown in Table 8, the electrode sheets prepared by mixing monomers A and B or monomer A in the electrode slurry and initiating in-situ polymerization of the monomers all passed the thermal shock test. The solid-state batteries prepared by mixing monomer B in the electrode slurry to initiate in-situ polymerization, the batteries containing monomer A or containing monomers A and B at the same time but without polymerization, and the solid-state batteries containing only D1 and D2 and the blank batteries did not pass the thermal shock test; and the batteries did not pass the thermal shock test when monomer A or A+B was introduced into the solid-state battery in the following ways: first, the monomer and the initiator were directly added to the electrolyte and then injected into the battery cell to initiate in-situ polymerization of the monomer to prepare the solid-state battery; second, the monomer and the initiator were prepared into a precursor solution and coated on the surface of the positive electrode, the negative electrode or the diaphragm, and then the monomer was polymerized in situ; third, the monomer polymerization was initiated in vitro to prepare a polymer material, and then mixed into the electrode slurry; fourth, the solid electrolyte was prepared by in-situ polymerization of the monomer and then the solid-state battery was assembled; further indicating that the present invention improves the safety of the battery. Moreover, if the content of phosphorus-based polymer material is too little, it is difficult to coat a thin layer of polymer material containing phosphorus groups on the surface of the electrode active material particles, and the battery will catch fire and explode during the thermal shock test, and the improvement of battery safety is not obvious; if the content of phosphorus-based polymer material is too much, the battery will not catch fire or explode during the thermal shock test, although it can greatly improve the safety of the battery, it will reduce the battery's energy density and cycle performance and other electrical properties. Mainly because the present application adopts the method of in-situ blending in the electrode slurry, so that the surface of the electrode active material particles is coated with a thin layer of polymer material containing phosphorus groups. Compared with general polymer electrolytes, this polymer layer has higher thermal stability and electrochemical stability, which can effectively reduce the surface activity of the electrode particles, reduce the direct contact between the active material particles and the electrolyte, inhibit the side reaction between the active material and the electrolyte, and improve the battery safety performance; in addition, the polymer layer can maintain a low interface impedance during the battery cycle, and at the same time homogenize the ion flow, so that the electrode has good capacity play and cycle stability, and ensures the electrochemical performance of the battery.
[0525] 3. Extrusion test: After fully charging the battery, place it in two planes and squeeze it perpendicular to the plate at a rate of 2mm / s. Stop squeezing when the voltage reaches 0V or the battery deformation reaches 50%. The battery passes the squeezing process if it does not catch fire or explode.
[0526] Table 9 Comparison of extrusion test results
[0527]
[0528] The present application provides an electrode sheet, which is prepared by mixing a phosphorus-based monomer containing a ring structure with an electrode slurry and then coating the mixture on a current collector, and then subjecting the mixture to in-situ polymerization to generate an electrode sheet containing a phosphorus-based polymer material. The solid-state battery prepared using the electrode sheet greatly improves the safety of the battery.
[0529] As shown in Table 9, the electrode sheets prepared by mixing monomers A and B or monomer A in the electrode slurry and initiating in-situ polymerization of the monomers all passed the extrusion test. The solid-state batteries prepared by mixing monomer B in the electrode slurry and initiating in-situ polymerization, the batteries containing monomer A or containing monomers A and B at the same time but without polymerization, and the solid-state batteries containing only D1 and D2 and the blank batteries did not pass the extrusion test; and the batteries also did not pass the extrusion test when monomer A or A+B was introduced into the solid-state battery in the following ways: first, the monomer and the initiator were directly added to the electrolyte and then injected into the battery cell to initiate the in-situ polymerization of the monomer to prepare the solid-state battery; second, the monomer and the initiator were prepared into a precursor solution and coated on the surface of the positive electrode, the negative electrode or the diaphragm, and then the monomer was polymerized in situ; third, the monomer polymerization was initiated in vitro to prepare a polymer material, and then mixed into the electrode slurry; fourth, the solid electrolyte was prepared by in-situ polymerization of the monomer and then the solid-state battery was assembled; further indicating that the present invention improves the safety of the battery.
[0530] In the puncture test, thermal shock safety test, and extrusion test, monomer A or monomers A and B were mixed in the electrode slurry and the monomers were polymerized in situ to prepare electrode sheets. All solid-state batteries prepared from the electrode sheets passed the test, and the solid-state batteries prepared by polymerizing both monomers A and B had better safety and better electrochemical performance. However, the monomers introduced into the solid-state battery by other means did not pass the safety test, such as directly adding the monomers and initiators to the electrolyte and then injecting them into the battery cell to initiate the in-situ polymerization of the monomers, preparing the monomers and initiators into precursor solutions and coating them on the positive electrode, negative electrode or diaphragm surface and then initiating the in-situ polymerization of the monomers, first initiating the polymerization of the monomers in vitro to prepare a polymer material, then mixing it into the electrode slurry, initiating the in-situ polymerization of the monomers to prepare a solid electrolyte, and then assembling the solid-state battery. However, the solid-state batteries and blank batteries in which monomers A or A+B were mixed into the electrode slurry but polymerization was not initiated, or monomer B was mixed into the electrode slurry and in-situ polymerization was initiated, or only D1 or D2 was mixed did not pass the safety test. Moreover, if the content of phosphorus-based polymer material is too little, the battery cannot pass the safety test because it is difficult to coat a thin layer of polymer material containing phosphorus groups on the surface of the electrode active material particles; if the content of phosphorus-based polymer material is too much, although it can greatly improve the safety of the battery, it will reduce the battery's electrical properties such as energy density and cycle performance. This shows that the phosphorus-based monomer containing a ring structure in the present application is mixed with the electrode slurry and then coated on the current collector. After in-situ polymerization, an electrode sheet containing a phosphorus-based polymer material is generated. The solid-state battery prepared using the electrode sheet greatly improves the safety of the battery. Moreover, for the same monomer, the positive and negative electrode slurries are simultaneously in-situ mixed, and the safety and electrical performance of the battery are also due to the in-situ mixing of the separate electrodes.
[0531] Based on previous research findings, the safety performance of lithium-ion batteries can be significantly improved by introducing the monomers involved in the present invention into the battery cell through general application methods, for example, in-situ polymerization is initiated after the monomers are injected into the battery cell, in-situ polymerization is initiated after the monomers are coated on the positive and negative electrodes or the surface of the diaphragm, etc. Although these solutions have been verified in 250-300Wh / kg battery cell samples for improving battery cell safety, and the corresponding battery cells can successfully pass puncture, extrusion, collision, 150°C thermal shock and other tests, the safety performance of batteries with higher specific energy (≥320Wh / kg) is not significantly improved. In order to obtain a battery with a specific energy of ≥320Wh / kg, the present invention increases the proportion of active materials in the battery cell, especially increases the surface capacity of the electrode, but these operations will make the chain reaction of thermal runaway in the battery cell more likely to occur, making the safety performance of high specific energy batteries more difficult to ensure; however, compared with the prior art, the technical solution provided by the present invention can further significantly improve the safety of the battery cell, and the 320Wh / kg high specific energy battery can successfully pass safety tests such as needle puncture and higher temperature thermal shock tests, that is, the technical solution of the present invention can ensure the safety performance of high specific energy batteries.
[0532] It should be noted that the monomer A in this patent, or the mixture of monomer A and monomer B, can also be directly used in combination with commercial electrolytes, and excellent results can still be achieved, indicating that the monomers used to prepare the polymer material in this application have good compatibility with various electrolytes.
[0533] In summary, the solid-state battery prepared by the present invention can not only significantly improve the battery safety performance, but also extremely well maintain the electrochemical performance of the battery, and is suitable for large-scale promotion and application.
[0534] In the present invention, only some structures are selected as representatives in the experimental examples to illustrate the preparation method and effects of the present application, and other structures not listed have similar effects.
[0535] The monomers used in the experimental examples can all be purchased or prepared simply, and the preparation processes are all existing technologies, so they are not described in detail in the specification.
[0536] It should also be noted that the applicant has conducted a large number of tests on this series of structures. Sometimes, in order to better compare with the existing system, the same structure and system have been tested more than once. Therefore, there may be certain errors in different tests.
[0537] Finally, it should be noted that the above-described embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
[0538] The preferred specific implementation modes and embodiments of the present application are described in detail above in conjunction with the accompanying drawings, but the present application is not limited to the above implementation modes, and various changes can be made within the knowledge scope of those skilled in the art without departing from the concept of the present application.
Claims
1. A high-safety electrode sheet, comprising a current collector and an electrode material covering the current collector, wherein the electrode material comprises an electrode active material, a conductive agent and a binder, and the high-safety electrode sheet is a positive electrode sheet or a negative electrode sheet; characterized in that: The electrode material also includes a phosphorus-based polymer material formed by polymerization of monomers; The phosphorus-based polymer material accounts for 0.05 to 10% by mass in the electrode material; Adding the monomer and the initiator during the electrode material slurry mixing process to polymerize in situ to form the phosphorus-based polymer material; In-situ polymerization conditions: in-situ polymerization temperature is 60-130°C, and in-situ polymerization time is 0.1-30min; The monomer includes monomer A; the monomer A is at least one of the compounds shown in formula I, Wherein, M1 is selected from any one of C, N, P, S, and Si; R1 is independently selected from any one of a chain or a ring with or without a substituent, and R1 contains at least one N; R2 to R4 are independently selected from any one of a chain or a ring with or without a substituent; represents a cyclic structure; A1 represents that any position of the cyclic structure can be substituted by a substituent.
2. The high-safety electrode sheet according to claim 1, characterized in that: The weight proportions of the components in the electrode material are: 80-99 parts of electrode active material, 0.5-10 parts of conductive agent, 0.5-10 parts of binder, and 0.1-10 parts of monomer.
3. The high-safety electrode sheet according to claim 1, characterized in that: R1 is selected from at least one of the compounds shown in formula II, Wherein, R7 is independently selected from any one of a chain or a ring with no, with or without a substituent; R8 is independently selected from any one of a chain or a ring with or without a substituent, and R8 contains at least one R9 is selected from any one of H, a chain or a ring which may or may not have a substituent.
4. The high-safety electrode sheet according to claim 1, characterized in that: The monomers also include monomer B; The monomer B is selected from at least one of the compounds shown in formula III, Wherein, M3 is selected from C, N, P, S, Si; R 12 ~R 13 R is independently selected from any one of a chain or a ring with no, with or without a substituent; 14 Independently selected from any one of a chain or a ring with or without a substituent.
5. The high-safety electrode sheet according to claim 4, characterized in that: R 14 It is selected from a ring or a chain containing at least one heteroatom, and any position of the ring or the chain can be substituted by a substituent.
6. The high-safety electrode sheet according to claim 4, characterized in that: R 14 is selected from a ring or chain containing at least two heteroatoms and containing at least one =0 in the ring or chain.
7. The high-safety electrode sheet according to claim 4, characterized in that: The molar ratio of the monomer B to the monomer A is α, wherein 0<α≤1.
8. A method for preparing a high-safety electrode sheet according to any one of claims 1 to 7, characterized in that: The method for preparing the high-safety electrode sheet comprises: (1) taking an electrode active material, a conductive agent, a binder, a monomer, and an initiator, and mixing them uniformly to prepare a mixed slurry; (2) coating the mixed slurry on a current collector and polymerizing the mixed slurry in situ to obtain the high-safety electrode sheet.
9. The preparation method according to claim 8, characterized in that: The mass of the initiator is 0.2% to 2% of the mass of the monomer; the coating condition is: the coating speed is 0.5 m / min to 80 m / min.
10. A battery, characterized in that: The invention comprises at least one of the high-safety electrode sheet described in any one of claims 1 to 7 and the high-safety electrode sheet obtained by the preparation method described in any one of claims 8 to 9.
